Modellbasierte Entwicklung von Ultraschallwandlern unter der Berücksichtigung von Nichtlinearitäten - Dymel, Collin
Ultraschallsysteme für das Herstellen für Bond- und Schweißverbindungen in der Halbleiterfertigung zeigen auf Grund des Betriebes unter hohen Anregungsniveaus nichtlineare Materialeigenschaften. Dabei wirken unterschiedliche Einflussfaktoren auf die elektrischen Eigenschaften und die mechanischen Übertragungscharakteristiken der Ultraschallsysteme ein. Die Herausforderungen ein solches geprägtes System auszulegen oder effizient und zuverlässig zu betreiben, sind aufgrund der Nichtlinearitäten relativ groß. Da für die Beschreibung der nichtlinearen Materialbeziehungen nur wenige Modelle und kaum quantitative Angaben vorliegen, werden die komplexen Wechselwirkungen von Materialparametern, Geometrie und Vorspannung des Schwingers, Betriebsgrößen (Strom, Spannung), Temperatur und Prozesslasten durch systematische Untersuchungen von Keramiken und Langevin-Schwingern messtechnisch erfasst. Aus den Messergebnissen werden einerseits eindimensionale Modelle für Voruntersuchungen als auch vollständige Materialparametersätze für die Simulation mittels dreidimensionaler FE-Modelle hergeleitet. Eine Methodik zur Ermittlung der Materialparameter und ein auf iterativen Simulationen von FE-Modellen basierendes Werkzeug zur Simulation der komplexen Wechselwirkungen werden vorgestellt. Anhand eines exemplarischen Ultraschallsystems wird gezeigt, dass die Wirkungen temperaturbedingter Vorspannungsverluste, Änderungen des elektrischen Klemmenverhaltens und Amplituden- und Frequenzänderungen während des Betriebes bei großen Amplituden und Prozesslasten durch die Variationen des Keramikvolumens und der Keramikposition positiv beeinflusst werden können.
Keywords: Nichtlineares piezoelektrisches Verhalten; Dehnungsabhängigkeit; Vorspannungseinfluss; Temperatureinfluss; Lasteinfluss; Langevin-Schwinger; Ultraschallwandler; Ultraschallbonden; FEM-Modell; Ultraschallschweißen; BVD-Modell

Diagnostics of Piezoelectric Bending Actuators Subjected to Varying Operating Conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Hemsel, Tobias; Sextro, Walter (Electronics)
In applications of piezoelectric actuators and sensors, the dependability and particularly the reliability throughout their lifetime are vital to manufacturers and end-users and are enabled through condition-monitoring approaches. Existing approaches often utilize impedance measurements over a range of frequencies or velocity measurements and require additional equipment or sensors, such as a laser Doppler vibrometer. Furthermore, the non-negligible effects of varying operating conditions are often unconsidered. To minimize the need for additional sensors while maintaining the dependability of piezoelectric bending actuators irrespective of varying operating conditions, an online diagnostics approach is proposed. To this end, time- and frequency-domain features are extracted from monitored current signals to reflect hairline crack development in bending actuators. For validation of applicability, the presented analysis method was evaluated on piezoelectric bending actuators subjected to accelerated lifetime tests at varying voltage amplitudes and under external damping conditions. In the presence of a crack and due to a diminished stiffness, the resonance frequency decreases and the root-mean-square amplitude of the current signal simultaneously abruptly drops during the lifetime tests. Furthermore, the piezoelectric crack surfaces clapping is reflected in higher harmonics of the current signal. Thus, time-domain features and harmonics of the current signals are sufficient to diagnose hairline cracks in the actuators.
Keywords: piezoelectric transducer; self-sensing; fault detection; diagnostics; hairline crack; condition monitoring

Einfluss der Radhubkinematik auf den Reifenverschleiß - Schütte, Jan; Sextro, Walter (20. VDI-Fachtagung Reifen - Fahrwerk - Fahrbahn)

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Experimental Investigation of Bond Formation and Wire Deformation in the Ultrasonic Wire Bonding Process - Scheidemann, Claus; Hagedorn, Oliver Ernst Caspar; Hemsel, Tobias; Sextro, Walter

Burst Mode of Ultrasonic Resonant Oscillations for Stimulation and Destruction of Tumor Cells - Sehlmeyer, Birte; Kampmann, Rebecca; Scheidemann, Claus; Hemsel, Tobias; Getzlaff, Mathias (Frühjahrstagung 2023, Sektion Kondensierte Materie (SKM))

Burst Mode Characteristics of an Ultrasonic Transducer for Treatment of Cancer Cells - Kampmann, Rebecca; Sehlmeyer, Birte; Scheidemann, Claus; Hemsel, Tobias; Getzlaff, Mathias (Frühjahrstagung 2023, Sektion Kondensierte Marterie (SKM))

Expert-Informed Hierarchical Diagnostics of Multiple Fault Modes of a Spacecraft Propulsion System - Aimiyekagbon, Osarenren Kennedy; Löwen, Alexander; Bender, Amelie; Muth, Lars; Sextro, Walter (Proceedings of the Asia Pacific Conference of the PHM Society 2023)
This paper presents a comprehensive study on diagnosing a spacecraft propulsion system utilizing data provided by the Prognostics and Health Management (PHM) society, specifically obtained as part of the Asia-Pacific PHM conference’s data challenge 2023. The objective of the challenge is to identify and diagnose known faults as well as unknown anomalies in the spacecraft’s propulsion system, which is critical for ensuring the spacecraft’s proper functionality and safety. To address this challenge, the proposed method follows a systematic approach of feature extraction, feature selection, and model development. The models employed in this study are kMeans clustering and decision trees combined to ensembles, enriched with expert knowledge. With the method presented, our team was capable of reaching high accuracy in identifying anomalies as well as diagnosing faults, resulting in attaining the seventh place with a score of 93.08 %.
Keywords: PHM; Fault Diagnostics; Multiple Fault Modes; Expert-Informed Diagnostics; Anomaly Detection

Transferability of a discrepancy model for the dynamics of electromagnetic oscillating circuits - Wohlleben, Meike Claudia; Muth, Lars; Peitz, Sebastian; Sextro, Walter (Proceedings in Applied Mathematics and Mechanics)
Modelling of dynamic systems plays an important role in many engineering disciplines. Two different approaches are physical modelling and data‐driven modelling, both of which have their respective advantages and disadvantages. By combining these two approaches, hybrid models can be created in which the respective disadvantages are mitigated, with discrepancy models being a particular subclass. Here, the basic system behaviour is described physically, that is, in the form of differential equations. Inaccuracies resulting from insufficient modelling or numerics lead to a discrepancy between the measurements and the model, which can be compensated by a data‐driven error correction term. Since discrepancy methods still require a large amount of measurement data, this paper investigates the extent to which a single discrepancy model can be trained for a physical model with additional parameter dependencies without the need for retraining. As an example, a damped electromagnetic oscillating circuit is used. The physical model is realised by a differential equation describing the electric current, considering only inductance and capacitance; dissipation due to resistance is neglected. This creates a discrepancy between measurement and model, which is corrected by a data‐driven model. In the experiments, the inductance and the capacity are varied. It is found that the same data‐driven model can only be used if additional parametric dependencies in the data‐driven term are considered as well.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Model-based condition monitoring of piezoelectric bending actuators - Bender, Amelie (Sensors and Actuators A: Physical)
With enhancing digitalization, condition monitoring is used in an increasing number of application fields across various industrial sectors. By its application, increased reliability as well as reduced risks and costs can be achieved. Based on different approaches, technical systems are monitored and measured data is analyzed to enable condition-based or predictive maintenance. To this end, machine learning approaches are usually implemented to diagnose the health states or predict the health index of the monitored system. However, these trained models are often black-box models, not intuitively explainable for a human. To overcome this shortcoming, a model-based approach based on physics is developed for piezoelectric bending actuators. Such a model enables a transparent representation of the system. Moreover, the model-based approach is extended by a parameter-estimation to account for sudden changes in behavior e. g. caused by occurring cracks.
Keywords: Condition Monitoring; Model-based approach Diagnostics; Varying conditions; Explainability; Piezoelectric bending actuators

Modellierung und Optimierung reibungsbasierter Ultraschall-Pulvertransportprozesse - Dunst, Paul
Der Transport feiner Pulver mit in der Regel sehr hohen adhäsiven und kohäsiven Eigenschaften stellt für viele konventionelle Transportsysteme eine große Herausforderung dar. Durch die Anwendung von Ultraschallschwingungen können insbesondere die hohen adhäsiven Kontaktkräfte und damit auch die Reibungseigenschaften manipuliert werden. Ein neu entwickeltes Pulvertransportsystem nutzt Ultraschallschwingungen, um die effektiven Tangentialkräfte im Pulver-Rohrkontakt zu reduzieren. Durch den koordinierten Einsatz von Ultraschallpulsen während einer niederfrequenten harmonischen Axialschwingung des Transportrohres wird ein kontinuierlicher Pulvertransport ermöglicht. Nach einer Einführung in die Grundlagen der Reibung und Reibungsmanipulation von Festkörpern und Pulvern sowie der Charakterisierung von Pulvern wird das Pulvertransportsystem auf Basis der Reibungsmanipulation inklusive der Leistungselektronik und der Ansteuerungshardware vorgestellt. Eine Sensitivitätsanalyse zeigt, dass die Anregungsparameter des Pulvertransportsystems ein großes Optimierungspotential aufweisen. Es wird ein effizientes, modulares Modell des Pulvertransportsystems vorgestellt, welches neben dem eigentlichen Modell des Transportprozesses ein Modell der Rohrschwingung und ein kennlinienbasiertes Modell des Pulver-Rohrkontakts beinhaltet. Mithilfe des Modells des Pulvertransportsystems werden Anregungsparameter hinsichtlich Amplituden und Frequenzen der auftretenden Schwingungen sowie der Schaltzeiten des Ultraschallpulses optimiert.
Keywords: Ultraschall; Pulvertransport; Modellierung; Optimierung; Reibung; Adhäsion; Kohäsion; Reibungsmanipulation

Predicting the Bond Quality of Heavy Copper Wire Bonds using a Friction Model Approach - Althoff, Simon
Ultraschall-Drahtbonden ist eine Standardtechnologie im Bereich der Aufbau- und Verbindungstechnik von Leistungshalbleitermodulen. Um Prozessschritte und damit wertvolle Zeit zu sparen, sollen die Kupferdickdrähte für die Leistungshalbleiter auch für die Kontaktierung von eingespritzten Anschlusssteckern im Modulrahmen verwendet werden. Das Kontaktierungsverfahren mit diesen Drähten auf Steckern in dünnwandigen Kunststoffrahmen führt häufig zu unzureichender Bondqualität. In dieser Arbeit wird das Bonden von Anschlusssteckern experimentell und anhand von Simulationen untersucht, um die Prozessstabilität zu steigern. Zunächst wurden Experimente auf Untergründen mit hoher Steifigkeit durchgeführt, um Störgrößen von Untergrundeigenschaften zu verringern. Die gewonnenen Erkenntnisse erlaubten die Entwicklung eines Simulationsmodells für die Vorhersage der Bondqualität. Dieses basiert auf einer flächenaufgelösten Reibarbeitsbestimmung im Fügebereich unter Berücksichtigung des Ultraschallerweichungseffektes und der hierdurch entstehenden hohen Drahtverformung. Experimente an den Anschlusssteckern im Modulrahmen zeigten eine verringerte Relativverschiebung zwischen Draht und Stecker, was zu einer deutlichen Verringerung der Reibarbeit führt. Außerdem wurden verminderte Schwingamplituden des Bondwerkzeugs nachgewiesen. Dies führt zu einer weiteren Reduktion der Reibarbeit. Beide Effekte wurden mithilfe eines Mehrmassenschwingers modelliert. Die gewonnenen Erkenntnisse und die erstellten Simulationsmodelle ermöglichen die Entwicklung von Klemmvorrichtungen, welche die identifizierten Störgrößen gezielt kompensieren und so ein verlässliches Bonden der Anschlussstecker im gleichen Prozessschritt ermöglichen, in dem auch die Leistungshalbleiter kontaktiert werden.
Keywords: heavy copper bonding; wire bonding; quality prediction; friction model; point-contact-element

Modellbasierte Ermittlung optimaler Prozessparameter für neuartige Ultraschallbondverbindungen - Scheidemann, Claus; Hemsel, Tobias; Sextro, Walter

Patent DE 10 2017 000 926 B4: Gerät mit wenigstens einem elastisch verformbaren Bauteil, insbesondere einem Gummi-Metall-Lager und mit einer Einrichtung zur Feststellung des Beginns einer verschleißbedingten Bauteil-Restnutzungsdauer, sowie Verfahren zur Bestimmung der Bauteil-Restnutzungsdauer. - Reinke, Kai; Bender, Amelie; Meyer, Tobias; Sextro, Walter; Kimotho, James Kuria
Die Erfindung betrifft ein Gerät mit wenigstens einem elastisch verformbaren Bauteil als Strukturteil und/oder Lagerteil, auf das im Betriebsverlauf von wechselnden Betriebszuständen abhängige, unterschiedliche Verformungskräfte einwirken, die zu einem die Bauteilnutzungsdauer begrenzenden Bauteilverschleiß führen, und mit einer Einrichtung zur Bestimmung der Bauteilnutzungsdauer und einer verschleißbedingten Bauteil-Restnutzungsdauer. Erfindungsgemäß wird ein sich zeitversetzt wiederholender, jeweils gleicher Betriebszustand vorbestimmt, dem eine jeweils gleiche, periodisch wirkende Verformungskraft zugeordnet ist, durch die das elastisch verformbare Bauteilmaterial periodisch verformt wird, wobei durch Walkarbeit ein Energieeintrag mit einem messbaren Temperaturanstieg im Vergleich zu einer Umgebungstemperatur erfolgt und wobei der jeweilige Temperaturanstieg als Kenngröße im Verlauf einer Bauteilnutzungsdauer entsprechend einer abnehmenden Bauteilsteifigkeit größer wird. Ein solcher vorbestimmter Betriebszustand wird jeweils von einer Messund Auswerteeinheit erkannt und ein Messvorgang durch ein Startsignal selbsttätig gestartet, wobei mit wenigstens einem bauteilzugeordneten Temperatursensor, der aktuelle Temperaturanstieg im Vergleich zur Umgebungstemperatur als Kenngröße für eine aktuelle Bauteilsteifigkeit gemessen und jeweils in einer Messkurve gespeichert und verglichen wird.

Experimental Investigation of Multidimensional Ultrasonic Heavy Wire Bonding - Scheidemann, Claus; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (2022 IEEE 9th Electronics System-Integration Technology Conference (ESTC))
ue to the constantly growing energy demand of power electronics and the need to reduce the size of electronic components like power modules for e-mobility, new challenges arise for ultrasonic wire bonding: the electrical connection must endure higher thermal and mechanical stress while the connecting partners become more sensitive or require more energy to get bonded. Past investigations have shown already that multi-dimensional ultrasonic bonding and welding yield the same or even better bond quality while reducing the load on the components. This contribution is intended to show whether multidi-mensional thick wire bonding is a promising concept to over-come the new challenges. The focus is on experimental investi-gations of different bond tool trajectories in ultrasonic wire bonding of aluminum and copper wire on DCB's and chips. The bond quality is analyzed by shear tests, microsections and, in the case of aluminum bonding, by a new machine learning method for an objective automated evaluation of the sheared area.

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Condition Monitor)

Experimental Investigation of the Influence of different Bond Tool Grooves on the Bond Quality for Ultrasonic Thick Wire Bonding - Hagedorn, Oliver Ernst Caspar; Broll, Marian; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (CIPS 2022 - 12th International Conference on Integrated Power Electronics Systems)
To achieve optimum bond results at ultrasonic bonding thick copper wire on sensitive components is quite challenging. Bearing in mind that high normal force and ultrasonic power are needed for bond quality but as well increase stress and finally failure risk of the substrate, methods should be found to achieve high bond quality even at lower bond parameters. Therefore, bond experiments with different bond tool grove geometries have been conducted for copper and aluminum wire on direct copper bonded (DCB) substrates to investigate the impact of geometric parameters on bond formation and bond quality. The wire material depending impact of geometry changes on the bond formation and deformation was quantified. Additionally, a bonding parameter design of experiments (DOE) has been conducted for the reference and the most promising groove geometry. Higher shear values were achieved at reduced vertical tool displacement for most bonding parameter combinations, compared to the reference tool. This behavior allows for reducing ultrasonic power to obtain equal shear values; consequently, mechanical stresses in the interface decrease. This could potentially reduce the risk of chip damage and thus yield loss.

Development of a Hybrid Modeling Methodology for Oscillating Systems with Friction - Wohlleben, Meike Claudia; Bender, Amelie; Peitz, Sebastian; Sextro, Walter (Machine Learning, Optimization, and Data Science)

Enhanced process development by simulation of ultrasonic heavy wire bonding - Schemmel, Reinhard
Das Ultraschall-Dickdrahtbonden mit Aluminiumdraht ist ein Standardverfahren zur elektrischenKontaktierung von Leistungshalbleitermodulen. Die steigenden Anforderungen an die Effizienzund Zuverlässigkeit der Module haben zu technologischen Weiterentwicklungen geführt und eswerden vermehrt Kupferdrähte mit wesentlich besseren elektrischen und thermischen Eigenschafteneingesetzt. Hieraus resultieren durch höhere Prozesskräfte und Ultraschallleistung neueHerausforderungen bei der Prozessentwicklung; hierfür wird ein Simulationsmodell zur Verbesserungder Prozessentwicklung entwickelt.In Ultraschall-Drahtbondversuchen mit 400 m Aluminium und Kupfer Drähten wurde der Einflussder Prozessparameter auf die Bondqualität untersucht; diese Ergebnisse und zusätzliche Messungender Drahtdeformation und Schwingungen wurden für die Formulierung der Anforderungenund zur Validierung der Ergebnisse des Simulationsmodells genutzt.Es wurde ein Prozessmodell, basierend auf einer Co-Simulation zwischen MATLAB und ANSYS,entwickelt; hierbei wurden die phyiskalischen Phänomene wie die Ultraschall Werkstoffentfestigung,der Verbindungsaufbau und die dynamischen Systemeigenschaften abgebildet.Basierend auf einer Zug-Druck-Prüfmaschine wurde ein Prüfstand zur Identifikation der Modellparameterentwickelt. In zusätzlichen Druckversuchen mit den Bonddrähten mit und ohneUltraschallanregung wurde die Reduktion der Umformkräfte unter Ultraschalleinfluss untersucht.Mit dem entwickelten Prozessmodell wurden die Parameterstudien aus den Ultraschall-Drahtbondversuchensimuliert und direkt mit den experimentellen Ergebnissen verglichen, wobei sich einerelativ gute Übereinstimmung zwischen Simulation und Messung sowohl für Aluminium, als auchfür Kupfer, erzielen ließ.

Piezoelectric Ultrasonic Power Transducers - Hemsel, Tobias; Twiefel, Jens (Reference Module in Materials Science and Materials Engineering)
This article is dedicated to piezoelectric ultrasonic power transducers that differ to well known medical ultrasonic diagnostic apparatus or non destructive testing devices by the level of power in use; typically several tens of up to more than thousand watts are used in a multitude of different applications. After a short introduction including historical development, the first focus is on theoretical background of the operating principle, design and mechanical modeling. As piezoelectric elements transform electrical to mechanical energy and vice versa, equivalent circuit modeling is also described. After that, sample applications are delineated by the matter wherein ultrasound generates unique effects: incredible high pressure level as well in air as in water, micro-bubbles generating temperature peaks for very short time instances in fluids, acoustoplastic effect, enhancement of diffusion and recrystallization in solids, friction manipulation, incremental deformation and micro-cracking of surfaces, or even generation of macroscopic movements in motors. At the end, some future directions ranging from novel modeling approaches to advanced control and new materials are addressed.
Keywords: Equivalent circuit model; Langevin transducer; Lumped parameter model; Piezoelectric transducer; Ultrasonic processes; Ultrasound

Generation of a Reduced, Representative, Virtual Test Drive for Fast Evaluation of Tire Wear by Clustering of Driving Data - Muth, Lars; Noll, Christian; Sextro, Walter (Advances in Dynamics of Vehicles on Roads and Tracks II - Proceedings of the 27th Symposium of the International Association of Vehicle System Dynamics, IAVSD 2021)
Tire and road wear are a major source of emissions of nonexhaust particulate matter (PM) and make up the largest share of microplastics in the environment. To reduce tire wear through numerical optimization of a vehicle's suspension system, fast simulations of the representative usage of a vehicle are needed. Therefore, this contribution evaluates if instead of a full simulation of a representative test drive, only specific driving maneuvers resulting from a clustering of the driving data can be used to predict tire wear. As a measure for tire wear, the friction work between tire and road is calculated. It is shown that enough clusters result in negligible deviations between the total friction work of the full simulation and the cluster simulations as well as between the distributions of the friction work over the tire width. The calculation time can be reduced to about 1% of the full simulation.
Keywords: Tire Wear; Vehicle Dynamics; Clustering; Virtual Test

Tire Wear Reduction Based on an Extended Multibody Rear Axle Model - Schütte, Jan; Sextro, Walter (Vehicles)
To analyze the influence of suspension kinematics on tire wear, detailed simulation models are required. In this study, a non-linear, flexible multibody model of a rear axle system is built up in the simulation software MSC Adams/View. The physical model comprises the suspension kinematics, compliance, and dynamics as well as the non-linear behavior of the tire using the FTire model. FTire is chosen because it has a separate tire tread model to compute the contact pressure and friction force distribution in the tire contact patch. To build up the simulation model, a large amount of data is needed. Bushings, spring, and damper characteristics are modeled based on measurements. For the structural components (e.g., control arms), reverse engineering techniques are used. The components are 3D-scanned, reworked, and included as a modal reduced finite element (FE)-model using component mode synthesis by Craig–Bampton. Finally, the suspension model is validated by comparing the simulated kinematic and compliance characteristics to experimental results. To investigate the interaction of suspension kinematics and tire wear, straight line driving events, such as acceleration, driving with constant velocity, and deceleration, are simulated with different setups of wheel suspension kinematics. The influence of the setups on the resulting friction work between tire and road is examined, and an exemplarily calculation of tire wear based on a validated FTire tire model is carried out. The results demonstrate, on the one hand, that the chosen concept of elasto-kinematic axle leads to a relatively good match with experimental results and, on the other hand, that there are significant possibilities to reduce tire wear by adjusting the suspension kinematics.

Identification of joints for a load-adapted shape in a body in white using steady state vehicle simulations - Martin, Sven; Schütte, Jan; Bäumler, C.; Sextro, Walter; Tröster, Thomas (Forces in Mechanics)

Rule-based Diagnostics of a Production Line - Aimiyekagbon, Osarenren Kennedy; Muth, Lars; Wohlleben, Meike Claudia; Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
In the industry 4.0 era, there is a growing need to transform unstructured data acquired by a multitude of sources into information and subsequently into knowledge to improve the quality of manufactured products, to boost production, for predictive maintenance, etc. Data-driven approaches, such as machine learning techniques, are typically employed to model the underlying relationship from data. However, an increase in model accuracy with state-of-the-art methods, such as deep convolutional neural networks, results in less interpretability and transparency. Due to the ease of implementation, interpretation and transparency to both domain experts and non-experts, a rule-based method is proposed in this paper, for prognostics and health management (PHM) and specifically for diagnostics. The proposed method utilizes the most relevant sensor signals acquired via feature extraction and selection techniques and expert knowledge. As a case study, the presented method is evaluated on data from a real-world quality control set-up provided by the European prognostics and health management society (PHME) at the conference’s 2021 data challenge. With the proposed method, our team took the third place, capable of successfully diagnosing different fault modes, irrespective of varying conditions.
Keywords: PHME 2021; Feature Selection Classification; Feature Selection Clustering; Interpretable Model; Transparent Model; Industry 4.0; Real-World Diagnostics; Quality Control; Predictive Maintenance

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Proceedings of the Seventeenth International Conference on Condition Monitoring and Asset Management (CM 2021))
Several methods, including order analysis, wavelet analysis and empirical mode decomposition have been proposed and successfully employed for the health state estimation of technical systems operating under varying conditions. However, where information such as the speed of rotating machinery, component specifications or other domain-specific information is unavailable, such methods are often infeasible. Thus, this paper investigates the application of classical time-domain features, features from the medical field and novel features from the highly comparative time-series analysis (HCTSA) package, for the health state estimation of rotating machinery operating under varying conditions. Furthermore, several feature selection methods are investigated to identify features as viable health indicators for the diagnostics and prognostics of technical systems. As a case study, the presented methods are evaluated on real-world and experimentally acquired vibration data of bearings operating under varying speed. The results show that the selected features can successfully be employed as health indicators for technical systems operating under varying conditions.
Keywords: Wind turbine diagnostics; bearing diagnostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection; fault detection; failure detection

Hybrid Prediction Method for Remaining Useful Lifetime Estimation Considering Uncertainties - Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
Predictive Maintenance as a desirable maintenance strategy in industrial applications relies on suitable condition monitoring solutions to reduce costs and risks of the monitored technical systems. In general, those solutions utilize model-based or data-driven methods to diagnose the current state or predict future states of monitored technical systems. However, both methods have their advantages and drawbacks. Combining both methods can improve uncertainty consideration and accuracy. Different combination approaches of those hybrid methods exist to exploit synergy effects. The choice of an appropriate approach depends on different requirements and the goal behind the selection of a hybrid approach. In this work, the hybrid approach for estimating remaining useful lifetime takes potential uncertainties into account. Therefore, a data-driven estimation of new measurements is integrated within a model-based method. To consider uncertainties within the system, a differentiation between different system behavior is realized throughout diverse states of degradation. The developed hybrid prediction approach bases on a particle filtering method combined with a machine learning method, to estimate the remaining useful lifetime of technical systems. Particle filtering as a Monte Carlo simulation technique is suitable to map and propagate uncertainties. Moreover, it is a state-of-the-art model-based method for predicting remaining useful lifetime of technical systems. To integrate uncertainties a multi-model particle filtering approach is employed. In general, resampling as a part of the particle filtering approach has the potential to lead to an accurate prediction. However, in the case where no future measurements are available, it may increase the uncertainty of the prediction. By estimating new measurements, those uncertainties are reduced within the data-driven part of the approach. Hence, both parts of the hybrid approach strive to account for and reduce uncertainties. Rubber-metal-elements are employed as a use-case to evaluate the developed approach. Rubber-metal-elements, which are used to isolate vibrations in various systems, such as railways, trucks and wind turbines, show various uncertainties in their behavior and their degradation. Those uncertainties are caused by diverse inner and outer factors, such as manufacturing influences and operating conditions. By expert knowledge the influences are described, analyzed and if possible reduced. However, the remaining uncertainties are considered within the hybrid prediction method. Relative temperature is the selected measurand to describe the element’s degradation. In lifetime tests, it is measured as the difference between the element’s temperature and the ambient temperature. Thereby, the influence of the ambient temperature on the element’s temperature is taken into account. Those elements show three typical states of degradation that are identified within the temperature measurements. Depending on the particular state of degradation a new measurement is estimated within the hybrid approach to reduce potential uncertainties. Finally, the performance of the developed hybrid method is compared to a model-based method for estimating the remaining useful lifetime of the same elements. Suitable performance indices are implemented to underline the differences between the results.
Keywords: Hybrid prediction method; Multi-model particle filtering; Uncertainty quantification; RUL estimation

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Zustandsüberwachung zur Prognose der Restlebensdauer von Gummi-Metall-Elementen unter Berücksichtigung systembasierter Unsicherheiten - Bender, Amelie
Eine zustandsbasierte Instandhaltungsstrategie reduziert das Risiko eines Ausfalls eines technischen Systems bei gleichzeitig hoher Ausnutzung und planbaren Instandhaltungsmaßnahmen. Das Ziel dieser Arbeit liegt in der Entwicklung einer Zustandsüberwachung für Gummi-Metall-Elemente. Die Herausforderungen dieser Zustandsüberwachung leiten sich aus dem viskoelastischen Verhalten sowie dem komplexen Degradationsverhalten der Elemente ab. Infolge der daraus resultierenden Unsicherheiten werden die Elemente heutzutage präventiv instandgehalten. In Lebensdauerversuchen der Gummi-Metall-Elemente werden drei Messgrößen detektiert. Dabei wird mit der Temperatur eine Messgröße identifiziert, die am geeignetsten zur Beschreibung des Zustands der Elemente ist. Generell wird die Genauigkeit einer Zustandsüberwachung durch verschiedene Unsicherheiten beeinflusst. Für die Prognose der nutzbaren Restlebensdauer der Gummi-Metall-Elemente wird das Partikelfilter, eine verbreitete modellbasierte Methode zur Zustandsüberwachung technischer Systeme, weiterentwickelt, um Unsicherheiten im Verhalten und der Degradation der Elemente zu berücksichtigen. Anhand der Ergebnisse wird belegt, dass aufbauend auf dieser Zustandsüberwachung die Ausnutzung der Gummi-Metall-Elemente in realen Anwendungen durch eine präventive Instandhaltung erhöht werden kann. Damit bildet diese Arbeit die Basis für zukünftige, prädiktive Instandhaltungskonzepte für diese Elemente. Weiterhin bestätigt die Arbeit, dass eine Berücksichtigung vorliegender Unsicherheiten zu einem frühen Zeitpunkt im Entwicklungsprozess des Zustandsüberwachungssystems empfehlenswert ist.
Keywords: Zustandsüberwachung; Prognose der Restlebensdauer; modellbasierte Prognose; Partikelfilter; Unsicherheiten; Gummi; Verlässlichkeit; Lebensdauerversuche; Predictive Maintenance

Prozessgerechte Gestaltung von Werkzeugen auf Basis von Verschleißsimulationen am Beispiel des Ultraschallbondens - Eichwald, Paul

A Multi-Model-Particle Filtering-Based Prognostic Approach to Consider Uncertainties in RUL Predictions - Bender, Amelie (Machines)
While increasing digitalization enables multiple advantages for a reliable operation of technical systems, a remaining challenge in the context of condition monitoring is seen in suitable consideration of uncertainties affecting the monitored system. Therefore, a suitable prognostic approach to predict the remaining useful lifetime of complex technical systems is required. To handle different kinds of uncertainties, a novel Multi-Model-Particle Filtering-based prognostic approach is developed and evaluated by the use case of rubber-metal-elements. These elements are maintained preventively due to the strong influence of uncertainties on their behavior. In this paper, two measurement quantities are compared concerning their ability to establish a prediction of the remaining useful lifetime of the monitored elements and the influence of present uncertainties. Based on three performance indices, the results are evaluated. A comparison with predictions of a classical Particle Filter underlines the superiority of the developed Multi-Model-Particle Filter. Finally, the value of the developed method for enabling condition monitoring of technical systems related to uncertainties is given exemplary by a comparison between the preventive and the predictive maintenance strategy for the use case.
Keywords: prognostics; RUL predictions; particle filter; uncertainty consideration; Multi-Model-Particle Filter; model-based approach; rubber-metal-elements; predictive maintenance

Application and modelling of ultrasonic transducers using 1-3 piezoelectric composites with structured electrodes - Dreiling, Dmitrij; Itner, Dominik; Feldmann, Nadine; Scheidemann, Claus; Gravenkamp, Hauke; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)
Waveguide-based methods can be used for the non-destructive determination of acoustic material parameters. One of these methods is based on transmission measurements of cylindrical polymeric specimens. Here, the experimental setup consists of two transducers, which excite and receive the waveguide modes at the faces of the cylinder. The measurement, as well as a forward model, are used to determine material parameters of the polymeric specimen in an inverse approach. 1-3 piezoelectric composites are used as an active element because they can be approximated by a thickness vibration only. This allows an easy identification of Mason model parameters to characterise the transducers’ vibration behaviour. However, sensitivity analysis shows a high uncertainty in the determination of the mechanical shear parameters due to the uniform excitation. To increase the sensitivity to these shear motions, arbitrary excitations were investigated by means of numerical simulation. In order to be able to realise the determined optimal excitation, new transducer prototypes were designed. By subdividing the electrodes of the active element, for example, ring-shaped excitation is feasible. Furthermore, it can be shown that modelling these transducers with a one-dimensional Mason model is sufficient.

Extraktion und Selektion geeigneter Merkmale für die Restlebensdauerprognose von technischen Systemen trotz aleatorischen Unsicherheiten - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (VDI-Berichte 2391)
Aufgrund der Fortschritte der Digitalisierung finden Systeme zur Zustandsüberwachung vermehrt Einsatz in der Industrie, um durch eine zustandsbasierte oder eine prädiktive Instandhaltung Vorteile, wie eine verbesserte Zuverlässigkeit und geringere Kosten zu erzielen. Dabei beruhen Zustandsüberwachungssysteme auf den folgenden Bausteinen: Sensorik, Datenvorverarbeitung, Merkmalsextraktion und -auswahl, Diagnose bzw. Prognose sowie einer Entscheidungsfindung basierend auf den Ergebnissen. Jeder dieser Bausteine erfordert individuelle Einstellungen, um ein geeignetes Zustandsüberwachungssystem für die jeweilige Anwendung zu entwickeln. Eine offene Fragestellung im Bereich der Zustandsüberwachung ergibt sich aufgrund der Unsicherheit der Zukunft, die sich in den zukünftigen Betriebs- und Umgebungsbedingungen zeigt. Diese Unsicherheit gilt es in allen Bausteinen zu berücksichtigen. Dieser Beitrag konzentriert sich auf den Baustein Merkmalsextraktion und -selektion, mit dem Ziel anhand geeigneter Merkmale eine Prognose der nutzbaren Restlebensdauer mit hoher Genauigkeit realisieren zu können. Daher werden geeignete Merkmale aus dem Zeitbereich und daraus abgeleitete Zustandsindikatoren für die Restlebensdauerprognose von technischen Systemen vorgestellt. Dabei sind Zustandsindikatoren Kenngrößen zur Beobachtung des Zustands der kritischen Systemkomponenten. Anhand dreier Anwendungsbeispiele wird ihre Eignung evaluiert. Dabei werden Daten aus Lebensdauerversuchen unter instationären Betriebs- und Umgebungsbedingungen ausgewertet. Die auftretenden Unsicherheiten der Zukunft werden somit berücksichtigt. Die Beispielsysteme beruhen auf Gummi-Metall-Elementen und Wälzlagern. Aus den generierten Ergebnissen lässt sich schließen, dass die Zustandsindikatoren aus der betrachteten Zeitreihen-Toolbox auch unter unbekannten Betriebs- und Umgebungsbedingungen robust sind.
Keywords: run-to-failure; rubber-metal element; bearing prognostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection

Model-Based Investigation of the Influence of Wheel Suspension Characteristics on Tire Wear - Schütte, Jan; Sextro, Walter (Lecture Notes in Mechanical Engineering)

Patent EP 3 358 332 B1: Verfahren zur Bestimmung des Beginns einer verschleißbedingten Bauteil-Restnutzungsdauer eines elastisch verformbaren Bauteils, als Strukturteil und/oder Lagerteil eines Geräts. - Reinke, Kai; Bender, Amelie; Meyer, Tobias; Sextro, Walter; Kimotho, James Kuria
Die Erfindung betrifft ein Gerät mit wenigstens einem elastisch verformbaren Bauteil als Strukturteil und/oder Lagerteil, auf das im Betriebsverlauf von wechselnden Betriebszuständen abhängige, unterschiedliche Verformungskräfte einwirken, die zu einem die Bauteilnutzungsdauer begrenzenden Bauteilverschleiß führen, und mit einer Einrichtung zur Bestimmung der Bauteilnutzungsdauer und einer verschleißbedingten Bauteil-Restnutzungsdauer. Erfindungsgemäß wird ein sich zeitversetzt wiederholender, jeweils gleicher Betriebszustand vorbestimmt, dem eine jeweils gleiche Verformungskraft zugeordnet ist, durch die das elastisch verformbare Bauteilmaterial verformt wird. Ein solcher vorbestimmter Betriebszustand wird jeweils von einer Mess- und Auswerteeinheit erkannt und ein Messvorgang durch ein Startsignal selbsttätig gestartet, wobei mit wenigstens einem bauteilzugeordneten Beschleunigungssensor, die aktuelle Beschleunigung der Verformung oder daraus abgeleitete Kennwerte als Kenngröße für eine aktuelle Bauteilsteifigkeit gemessen und jeweils in einer Messkurve gespeichert und verglichen wird.

Evaluation of time series forecasting approaches for the reliable crack length prediction of riveted aluminium plates given insufficient data - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (PHM Society European Conference)
In all fields, the significance of a reliable and accurate predictive model is almost unquantifiable. With deep domain knowledge, models derived from first principles typically outperforms other models in terms of reliability and accuracy. When it may become a cumbersome or an unachievable task to build or validate such models of complex (non-linear) systems, machine learning techniques are employed to build predictive models. However, the accuracy of such techniques is not only dependent on the hyper-parameters of the chosen algorithm, but also on the amount and quality of data. This paper investigates the application of classical time series forecasting approaches for the reliable prognostics of technical systems, where black box machine learning techniques might not successfully be employed given insufficient amount of data and where first principles models are infeasible due to lack of domain specific data. Forecasting by analogy, forecasting by analytical function fitting, an exponential smoothing forecasting method and the long short-term memory (LSTM) are evaluated and compared against the ground truth data. As a case study, the methods are applied to predict future crack lengths of riveted aluminium plates under cyclic loading. The performance of the predictive models is evaluated based on error metrics leading to a proposal of when to apply which forecasting approach.
Keywords: PHM 2019; crack propagation; forecasting; unevenly spaced time series; step ahead prediction; short time series

Experimental analysis and modelling of bond formation in ultrasonic heavy wire bonding - Schemmel, Reinhard; Scheidemann, Claus; Hemsel, Tobias; Kirsch, Olaf; Sextro, Walter (CIPS 2020; 11th International Conference on Integrated Power Electronics Systems)
Ultrasonic wire bonding is a process to form electrical connections in electronics well established industry. Typically, a clamping tool is pressed on the wire and forced to vibrate at relative high frequency 40 to 100 kHz. The ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes, contamination like oxide layers are removed from the contact zone, the surface roughness is reduced, and with increasing bond duration an metallic connection of wire and substrate is established. It is known that the amount of ultrasonic energy over time directly influences the strength and reliability of the bond connection, but the determination of optimum bond parameters is still a challenging experimental task. For this, in the past different model approaches have been presented, to calculate the bond quality by simulation. Measuring the friction between wire and substrate to validate these models is a challenging task at ultrasonic bonding frequency. Therefore a versatile test rig for bonding experiments at frequencies lower than 1 kHz is setup to get detailed insight into the different phases of the connection process. It includes a piezoelectric force sensor for the measurement of the three-dimensional process forces, an electrodynamic shaker for the vibration excitation and a conventional tension-compression testing machine to apply the bond normal force. Using this test rig, it is possible to observe the different phases of bond formation in detail, validate and enhance existing models and finally optimize bond parameters for different processes.

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (2020 21st International Conference on Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems (EuroSimE))

Schwingungen - Magnus, Kurt; Popp, Karl; Sextro, Walter
Schwingungsprobleme in der Technik analysieren, verstehen und beschreiben Schwingungen treten als nützliche oder auch als störende Erscheinungen fast überall in Natur und Technik auf. Deshalb ist es wichtig, sie zu verstehen, zu deuten oder auch in gewünschter Weise zu beeinflussen. Dieses Lehrbuch gibt eine Einführung in die physikalischen Grundlagen und die mathematische Behandlung von Schwingungen. In der aktuellen Auflage wurden der Text und die Bilder überarbeitet sowie konstruktive Hinweise von Fachkollegen berücksichtigt. Der Inhalt Grundbegriffe und Darstellungsmittel - Freie Schwingungen - Selbsterregte Schwingungen - Parametererregte Schwingungen - Erzwungene Schwingungen - Koppelschwingungen - Kontinuumsschwingungen - Chaotische Bewegungen - Aufgaben und Ergebnisse Die Zielgruppe Studierende der Ingenieurwissenschaften, der Physik und der Mathematik, berufstätige Ingenieure

Integrierte Modellierung von Zuverlässigkeit und dynamischem Verhalten mechatronischer Systeme - Kaul, Thorben
Die digitale Transformation prägt die Entwicklung intelligenter technischer Systeme, welche durch Vernetzung und inhärente Intelligenz einen weiten Funktionsumfang aufweisen. Selbstoptimierende Systeme sind als Stellvertreter der Klasse intelligenter Systeme durch die autonome zielkonforme Adaption des Systemverhaltens charakterisiert. Dabei stellen mechatronische Systeme eine der Grundlagen dieser Systemklasse dar, indem die Umwelt- und Betriebsbedingungen sowie die Systemzustände sensorisch erfasst und das dynamische Systemverhalten zielgerichtet beeinflusst werden. Der große Funktionsumfang intelligenter technischer Systeme geht mit einer Zunahme der Systemkomplexität einher, die eine Herausforderung bei der Absicherung der Verlässlichkeit darstellt. Dem gegenüber bieten insbesondere selbstoptimierende Systeme Potenziale zur Steigerung der Verlässlichkeit. Die Umsetzung entsprechender Maßnahmen erfordert die Unterstützung des Entwicklungsprozesses durch geeignete Methoden. Die Beherrschung der zunehmenden Systemkomplexität ist durch die Verwendung vorhandener Modelle des Entwicklungsprozesses möglich, wird aber in aktuellen Methoden nicht umfänglich genutzt. Das Ziel ist die Absicherung der Verlässlichkeit bereits in frühen Entwicklungsphasen bis hin in späte Lebenszyklusphasen. Es wird eine Methode für die integrierte Modellierung der Zuverlässigkeit, als zentrale Kenngröße der Verlässlichkeit, und des dynamischen Systemverhaltens entwickelt. Anhand von drei Anwendungsbeispielen wird gezeigt, dass diese Methode die Entwicklung von Maßnahmen zur Steigerung der Verlässlichkeit in selbstoptimierenden Systemen ermöglicht, auf komplexe Systeme anwendbar ist und die Absicherung der Verlässlichkeit während des Betriebs mit Hilfe eines Digitalen Zwillings unterstützt.
Keywords: Integrierte Modellierung; geschlossene Modellierung; mechatronische Systeme; intelligente Systeme; Zuverlässigkeit; Dynamische Bayes’sche Netze; Verlässlichkeit; Systemzuverlässigkeit; Digitaler Zwilling; selbstoptimierende Systeme; Mehrzieloptimierung

Halbachsprüfstand zur kinematischen, elastokinematischen und dynamischen Charakterisierung von Radaufhängungen - Schütte, Jan; Sextro, Walter; Kohl, Sergej (Fachtagung Mechatronik 2019)
Die Achse als einzige Verbindung zwischen Fahrzeugaufbau und Rad hat die Hauptaufgabe das Rad auf der Straße zuführen. Kinematisch betrachtet übernimmt die Radaufhängung, als Teil der Achse, die Funktion, zwischen Rad und Fahrzeugaufbaueinen vertikalen Freiheitsgrad zur Aufnahme von Fahrbahnunebenheiten zu realisieren. Die aus der RadhubundElastokinematik resultierenden Radstellungsänderungen bestimmen dabei maßgeblich die Fahrdynamik. Zur objektivenBeurteilung von Radaufhängungen ist eine genaue Charakterisierung der Radhub- und Elastokinematik erforderlich.Daher wurde zur Identifikation der kinematischen, elastokinematischen und dynamischen Radaufhängungseigenschaftenam Lehrstuhl für Dynamik und Mechatronik der Universität Paderborn ein Halbachsprüfstand entwickelt. Bei der Auslegungwurde Wert auf ein möglichst breites Einsatzspektrum gelegt. Es können verschiedene Typen von Einzelradaufhängungenin Serien- oder Prototypenkonfiguration am Prüfstand analysiert werden. Er ermöglicht eine Identifikation derdynamischen Radstellungsänderungen unter verschiedenen fahrdynamischen Lastfällen und regellosen Anregungen.

Digital Twin for Reliability Analysis During Design and Operation of Mechatronic Systems - Kaul, Thorben; Bender, Amelie; Sextro, Walter (Proceedings of the 29th European Safety and Reliability Conference (ESREL2019))
As the emerging digitalization of technical systems offers immense opportunities to be exploited by means of bigdata analysis, ubiquitous computing and largely networked systems, the digital twin comes into focus to combineall these aspects to an attendant model of an individual system during design phase as well as during operation.Since state-of-art technical systems are growing increasingly complex due to inherent intelligence and increasingfunctionality, i. e. autonomous behavior so far, it becomes considerably challenging to ensure reliability for thosesystems. Many methods were developed to support a reliability focused design or reliability-by-design approachesto tackle this challenge during design process. In field, data-based methods, i. e. condition monitoring enabled bythe rise of machine learning approaches, are exploited to ensure a reliable operation based on the current conditionof the monitored system. In order to take advantage of existing models of system reliability during design phaseand condition monitoring systems during operation, a method is proposed to combine both approaches in order toset up a digital twin with focus on system reliability. The base model of the digital twin is taken from the systemreliability model from the design phase and is used during operation and therein updated to the current reliabilitybased on the state estimation of the condition monitoring system. The approach is illustrated with a case study of arolling bearing test rig.

Remaining useful lifetime prediction based on adaptive failure thresholds - Bender, Amelie; Schinke, Lennart; Sextro, Walter (Proceedings of the 29th European Safety and Reliability Conference (ESREL2019))
Remaining useful lifetime (RUL) predictions as part of a condition monitoring system are focused in more and more research and industrial applications. To establish an efficient and precise estimate of the RUL of a technical product, different uncertainties have to be handled. To minimize the uncertainties of the RUL estimation, a reliable and accurate prognostic approach as well as a good failure threshold are important. Regarding the failure threshold, most often an expert sets a fixed failure threshold. However, neither the a priori known failure threshold nor a fixedthreshold value are feasible in every application. Especially in the case of varying characteristics of the monitored system, an adaptive failure threshold is of great importance concerning the accuracy of the RUL estimation. Rubber-metal-elements, which are used in a wide range of applications for vibration and sound isolation, are mon-itored by thermocouples to allow for lifetime predictions. Therefore, the element’s state is described by its temper-ature during its service life. Aiming to establish accurate RUL predictions of a rubber-metal-element, uncertainties due to nonlinear material characteristics and changing operational conditions have to be considered. Consequently, different temperature-based failure threshold definitions are implemented and compared within a particle filtering approach.
Keywords: RUL prediction; adaptive threshold; prognostics; condition monitoring

Impact of multi-dimensional vibration trajectories on quality and failure modes in ultrasonic bonding - Schemmel, Reinhard; Eacock, Florian; Dymel, Collin; Hemsel, Tobias; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (International Symposium on Microelectronics)
Ultrasonic joining is a common industrial process. To build electrical connections in the electronics industry, uni-axial and torsional ultrasonic vibration have been used to join different types of workpieces for decades. Many influencing factors like ultrasonic power, bond normal force, bond duration and frequency are known to have a high impact on bond quality and reliability. Multi-dimensional bonding has been investigated in the past to increase ultrasonic power and consequently bond strength. This contribution is focused on the comparison of circular, multi-frequency planar and uniaxial vibration trajectories used for ultrasonic bonding of copper pins on copper substrate. Bond quality was analyzed by shear tests, scanning acoustic microscopy and interface cross-sections.

Using complex multi-dimensional vibration trajectories in ultrasonic bonding and welding - Schemmel, Reinhard; Hemsel, Tobias; Dymel, Collin; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (Sensors and Actuators A: Physical)
Ultrasonic joining is a common industrial process. In the electronics industry it is used to form electrical connections, including those of dissimilar materials. Multiple influencing factors in ultrasonic joining are known and extensively investigated; process parameters like ultrasonic power, bond force, and bonding frequency of the ultrasonic vibration are known to have a high impact on a reliable joining process and need to be adapted for each new application with different geometry or materials. This contribution is focused on increasing ultrasonic power transmitted to the interface and keeping mechanical stresses during ultrasonic bonding low by using a multi-dimensional ultrasonic transducer concept. Bonding results for a new designed connector pin in IGBT-modules achieved by multi- and one-dimensional bonding are discussed.
Keywords: Ultrasonic bonding; Ultrasonic welding; Multi-dimensional bonding; Complex vibration; Multi-frequent; Two-dimensional friction model

Zeiteffiziente messtechnische Analyse glatt-nichtlinearen Schwingverhaltens dynamischer Strukturen - Sprock, Christian
Die Bestimmung des Frequenzübertragungsverhaltens von Strukturen mit nichtlinearer Charakteristik ist eine im technischen Bereich vielfach auftretende Aufgabe, z.B. für die genaue Bestimmung dynamischer Eigenschaften in der Entwurfsphase oder bei der Parametrierung von Modellen. Die typisch angewandten Verfahren zur Schwingungsmessung solcher Strukturen legen in der Regel ein lineares Strukturverhalten zu Grunde, oder sie erfordern einen hohen Zeit- und Messaufwand für die Abbildung des nichtlinearen Verhaltens; häufig in Verbindung mit einer starken Belastung der zu testenden Struktur. Die Bestimmung nichtlinearen Strukturverhaltens ist somit oft nicht effizient realisierbar. In der vorliegenden Arbeit wird ein neuer Ansatz zur Schwingungsanalyse nichtlinearer Strukturen mit von der Anregungsamplitude abhängigem Übertragungsverhalten vorgestellt. Dabei liegt ein Schwerpunkt auf der messtechnischen Bestimmung des nichtlinearen Verhaltens bei deutlich reduziertem Zeit- bzw. Messaufwand. Das Verfahren basiert auf einer Messmethode, die eine effiziente Bestimmung des nichtlinearen Kennfeldes der analysierten Struktur mit speziellen multiharmonischen Anregungssignalen ermöglicht. In Kombination mit einem fortschrittlichen Auswertealgorithmus kann eine vollständige Beschreibung des dynamischen Verhaltens in Form eines charakteristischen Diagramms generiert werden. Das Messverfahren wird durch eine Identifikationsroutine ergänzt, die die erforderliche Anzahl an Messungen nochmals reduzieren kann. Es ist als Mess-System auf Hard- und Software implementiert; der Funktionsnachweis erfolgt an verschiedenen Beispielen.
Keywords: Schwingungsanalyse; nichtlineare Strukturdynamik; Multisinus; Duffing-Schwinger; amplitudenabhängige Nichtlinearität; Peakbending; Backbone Curve; Schwingungsmessung; Frequenzverstimmung; Autoregression; Best Linear Approximation

Analyse der Reibleistungsverteilung im Reifenlatsch unter Berücksichtigung der Fahrwerkdynamik eines Mehrlenkerachssystems zur Bewertung des Reifenverschleißes - Kohl, Sergej
Durch die Auslegung eines Fahrwerks werden maßgebend die Fahrsicherheit, der Fahrkomfort, die Effizienz und der Fahrspaß eines Kraftfahrzeugs bestimmt. Daher zählt das Fahrwerk zu den wichtigsten und zugleich komplexesten Systemen in einem Automobil. Aufgrund steigender Kundenanforderungen, Auflagen durch Gesetzgebung sowie Termin- und Kostendruck stellt die Entwicklung des Fahrwerks für die heutigen Automobile stets eine Herausforderung dar. Um die gestellten Anforderungen zu erfüllen, sind oftmals gegenläufige Maßnahmen erforderlich, sodass die Auslegung des Fahrwerks in der Regel nur einen Kompromiss bildet. Entwicklungsziele zur Reduktion der Umweltbelastung und zur Effizienzsteigerung gewinnen hierbei zunehmend an Bedeutung. Damit verbunden müssen die Interaktionen zwischen Fahrwerk und Reifen hinreichend genau erfasst werden, sodass folglich eine Erweiterung bisheriger Simulationsmethoden erforderlich ist. In der vorliegenden Arbeit wird eine Vorgehensweise mit dem Schwerpunkt auf der Abbildung der Wechselwirkungen zwischen der Fahrwerkdynamik am Beispiel einer Mehrlenkerhinterachse und des Reifen-Fahrbahn-Rollkontakts entwickelt, die eine modellbasierte Analyse der Reibvorgänge in der Kontaktzone unter realitätsnahen Bedingungen ermöglicht. Vor allem können dadurch die Auswirkungen der Fahrwerkauslegung auf die Leistungsübertragung zwischen Reifen und Fahrbahn und den resultierenden Reifenverschleiß effektiv bewertet und bereits in der frühen Entwicklungsphase berücksichtigt werden.
Keywords: Reifenverschleiß; Reibleistung; Reifenlatsch; Reifen-Fahrbahn-Kontakt; Fahrbahnanregung; Mehrlenkerachse; Kinematik; Elastokinematik; Fahrwerkdynamik; Frequenz- und Amplitudenabhängigkeit; Modellierung; Validierung; Mehrkörpersimulation; MKS; ADAMS; FTire

Modellierung und experimentelle Charakterisierung der Wechselwirkung zwischen Ultraschallwandler und Flüssigkeit in kavitationsbasierten Prozessen - Bornmann, Peter
Ultraschall wird zur Effizienzsteigerung in verfahrenstechnischen Prozessen eingesetzt. Die Betriebsparamter der Ultraschallsysteme werden empirisch ermittelt, da derzeit keine systematische Analyse der Wechselwirkung zwischen Ultraschallwandler und Schallfeld sowie kein Verfahren zur Messung der Kavitationsaktivität ohne zusätzlichen Sensor existieren. Auf Basis einer experimentellen Analyse des betrachteten sonochemischen Reaktors wird ein Finite-Elemente-Modell aufgebaut, das die Wechselwirkung zwischen Schallfeld und Ultraschallwandler berücksichtigt. Die modellbasierte Analyse zeigt, dass wegen der akustischen Eigenschaften des Autoklavs nur direkt an der Sonotrode Kavitation entsteht. Die Wechselwirkung zwischen Ultraschallwandler und Schallfeld ermöglicht Aussagen über das Schallfeld und die Kavitationsaktivität auf Basis der Rückwirkung auf den Ultraschallwandler. Die lineare Schalldruckverteilung ermöglicht eine Prognose über die Verteilung von Kavitationszonen. Das beschriebene Modell liefert wertvolle Erkenntnisse für die Auslegung, Analyse und Skalierung sonochemischer Reaktoren. Auf Grund der rauen Prozessrandbedingungen ist die Applikation von Sensoren zur Überwachung der Kavitationsaktivität in vielen sonochemischen Prozessen nicht möglich. Zur prozessbegleitenden Messung der Kavitationsaktivität wird ein Verfahren entwickelt, das die Bewertung der Kavitationsaktivität durch Auswertung der Rückwirkung auf den Ultraschallwandler erlaubt. Das Messverfahren ermöglicht eine vorhersagbare und reproduzierbare Durchführung kavitationsbasierter Prozesse und stellt eine wichtige Erweiterung für bestehende und neue Ultraschallsysteme dar.
Keywords: Sonochemie; Akustische Kavitation; Kavitationsmessung; Kavitationsdetektion; FEM-Simulation Ultraschallwandler; Prozessüberwachung; FEM-Simulation Schallfeld; Self-Sensing; Piezoelektrische Ultraschallwandler; Ultraschallreinigung

Messung hochfrequenter In-Plane-Schwingungen mittels Laservibrometrie in räumlich eingeschränkten Umgebungen - Hagedorn, Oliver Ernst Caspar; Pielsticker, Daniel; Hemsel, Tobias; Sextro, Walter (2. VDI-Fachtagung Schwingungen 2019)

Atomization of Fluids with Ultrasound - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Sextro, Walter (Conference Proceedings - The 4th Conference on MicroFluidic Handling Systems (MFHS2019))
In a variety of industrial applications, liquids are atomized to produce aerosols for further processing. Example applications are the coating of surfaces with paints, the application of ultra-thin adhesive layers and the atomization of fuels for the production of combustible dispersions. In this publication different atomizing principles (standing-wave, capillary-wave, vibrating-mesh) are examined and discussed. Using an optimized standing-wave system, tough liquids with viscosities of up to about 100 Pas could be successfully atomized.
Keywords: atomization; ultrasound; standing-wave; capillarywave; vibrating-mesh

Konstruktion und Zustandsüberwachung eines Gummi-Metall-Teils mit integriertem Thermoelement - Bender, Amelie; Reinke, Kai; Sextro, Walter (10. VDI-Fachtagung Schwingungen von Windenergieanlagen 2019)
Gummi-Metall-Teile (GM-Teile) werden zur Schwingungsreduktion u. a. in Windenergieanlagen eingesetzt. Mögliche Anwendungen der Teile liegen in Wellen-, Generator- und Getriebelagerungen, Lagern für die Gondel und ihre Komponenten sowie in Drehmomentstützen. Mit dem Ziel eine prädiktive Instandhaltung zu realisieren, soll eine Zustandsüberwachung für die GM-Teile entwickelt werden. Diese Entwicklung basiert auf der Umsetzung diverser Schritte. Neben der funktionalen Betrachtung wird zwingend auch die konstruktive Integration der Sensoren in das überwachte Teil berücksichtigt. Der Schwerpunkt dieser Arbeit liegt auf der verwendeten Messgröße Temperatur, die mittels ausgewählter Sensorik detektiert wird. Dabei werden Lebensdauerversuche unter instationären Betriebsbedingungen durchgeführt, um diese Messdaten zu generieren. In der Datenauswertung werden sie hinsichtlich der Degradierung des GM-Teils analysiert und für die Ermittlung der nutzbaren Restlebensdauer verwendet. Rubber-metal-elements are used for isolation of vibrations e. g. in wind turbines. Possible applications of the elements are shaft bearings, generator bearings, gearbox bearings, bearings for the nacelle and its components and torque supports. In order to realize predictive maintenance, an accurate condition monitoring system for rubber-metal-elements should be developed. During that development different aspects have to be implemented. Additionally to the functional analysis, the constructive integration of the sensors into the monitored part is mandatory. The focus of this work is on the measured variable temperature, which is detected by means of appropriate sensors. Thereby lifetime tests are run under non-stationary operating conditions to generate temperature measurements. During data analysis, the measured data is analyzed regarding the degradation of the rubber-metal-elements and remaining useful lifetimes are estimated.

Integration von Verlässlichkeitsmodellen der Entwicklung in einen Digitalen Zwilling zur Umsetzung einer vorausschauenden Instandhaltung - Kaul, Thorben; Hentze, Julian; Sextro, Walter; Gräßler, Iris (Fachtagung Mechatronik 2019 Paderborn)
In der Entwicklung mechatronischer Systeme spielt die Steigerung der Verlässlichkeit und somit auch der Zuverlässigkeit und der funktionalen Sicherheit eine entscheidende Rolle. Die modellbasierte Entwicklung liefert in Kombination mit unterstützender Software einen wichtigen Beitrag zur Absicherung der Verlässlichkeit mechatronischer Systeme in frühen Entwicklungsphasen. In der Nutzungsphase ermöglichen aktuelle Verfahren der Zustandsüberwachung und moderne Methoden der Regelungstechnik eine effektive Absicherung. Modelle aus der Entwicklung mechatronischer Systeme enthalten weitreichende Informationen über die Architektur, das Verhalten und die Verlässlichkeit eines Systems. Diese Modelle können als Grundlage für die Erstellung eines Digitalen Zwillings für die vorausschauende Instandhaltung verwendet und mit Zustandsdaten des realen Systems kombiniert werden. Die Nutzung der Modelle für den Digitalen Zwilling bietet weitreichende Potenziale und vereinfacht dessen Erzeugung. Die Veröffentlichung beschreibt Rahmenbedingungen der Integration und stellt die Potenziale des Digitalen Zwillings zur vorausschauenden Instandhaltung dar.

Modellbasierte und experimentelle Charakterisierung von intensiven Ultraschall-Stehwellenfeldern für die Zerstäubung hochviskoser Flüssigkeiten - Dunst, Paul; Hemsel, Tobias; Bornmann, Peter; Littmann, Walter; Sextro, Walter (DAGA 2019)
Für die Zerstäubung hochviskoser Flüssigkeiten werden neben Düsenzerstäubern vor allem UltraschallStehwellenzerstäuber angewendet [1]. Diese ermöglichen ohne weitere Maßnahmen zwar keine gerichtete Zerstäubung, benötigen jedoch im Gegensatz zu Düsenzerstäubern keine hohen Drücke und haben keine hohen Austrittsgeschwindigkeiten. Zur Erzeugung der Ultraschallwellen werden typischerweise piezoelektrische, mit Bolzen verschraubte LangevinWandler verwendet [1-4], die eine starke Schallabstrahlung bei einer elektrischen Eingangsleistung von bis zu einigen Kilowatt erzeugen können. Wie bei jedem anderen schwingenden System emittiert der Ultraschallwandler zunächst eine Wanderwelle. Mit einem Reflektor, der gegenüber der Sonotrode angeordnet ist, wird eine stehende Welle erzeugt. Im Resonanzabstand zwischen Reflektor und Wandler werden abgestrahlte und reflektierte Wellen so überlagert, dass höhere Schalldruckamplituden erzielt werden. Ein einfacher Ansatz zur Maximierung des Schallpegels im Stehwellenfeld ist die Erhöhung der Schwingungsamplituden des Wandlers, die jedoch zu Schäden oder zumindest zu einer Verringerung der Lebensdauer führen kann. Hohe Schalldrücke werden auch bei geringen Abständen zwischen Wandler und Reflektor erreicht. Das Volumen des Schallfeldes ist in diesem Fall jedoch für die meisten Prozesse zu klein. Ein weiterer Ansatz ist die Verwendung zweier entgegengesetzt angeordneter Wandler [5]. In diesem Fall erfordert jedoch die Erzeugung einer stehenden Welle eine genaue Abstimmung von Frequenz und Phase beider Wandler, was eine komplexe Steuerung erfordert. Ebenso ist es möglich, geometrische Randbedingungen des Stehwellensystems zu optimieren, sodass es zu optimaler Interferenz der Wellen kommt. Im Folgenden wird der Anschaulichkeit halber vereinfachend angenommen, dass der Wandler an seiner Sonotrodenoberfläche einzelne Schallstrahlen aussendet, die in Nähe des Wandlers nahezu parallel verlaufen und sich mit zunehmender Entfernung vom Wandler auffächern. Ein einfaches Stehwellensystem, bestehend aus ebener Sonotrode und ebenem Reflektor, erzeugt bei kleinem Abstand zwischen Sonotrode und Reflektor sehr hohe Schallpegel, da nahezu sämtliche ausgesandten Schallstrahlen in Richtung der Sonotrode reflektiert werden positive Interferenz entsteht. Erhöht man jedoch den Abstand zwischen Sonotrode und Reflektor, so nehmen die Verluste durch Schallstrahlen, die den Prozessraum verlassen, zu. Wie Abbildung 1 gezeigt, werden nur Schallstrahlen, die in etwa parallel zur Rotationsachse verlaufen, zum Wandler zurück reflektiert und tragen zum Stehwellenfeld bei. Die Strahlen haben zudem abhängig vom Abstrahlwinkel unterschiedliche Weglängen. Die Stehwellenbedingung ist demnach nur für Strahlen in der Nähe der Rotationsachse exakt erfüllt. Um dies zu vermeiden, müssen die Geometrien von Wandler und Reflektor optimiert werden. In den folgenden Abschnitten wird zunächst ein Optimierungsansatz vorgestellt. Mithilfe eines FiniteElemente-Modells werden die Auswirkungen einer optimierten Geometrie auf den maximalen Schalldruckpegel untersucht. Ergebnisse werden durch Messungen an einem experimentellen Aufbau eines Stehwellensystems validiert. Es wird gezeigt, wie sich die Optimierung der geometrischen Randbedingungen auf die Zerstäubung hochviskoser Flüssigkeiten auswirkt.

Intelligente Herstellung zuverlässiger Kupferbondverbindungen - Sextro, Walter; Brökelmann, Michael
Dieses Buch beschreibt basierend auf dem gleichnamigen Innovationsprojekt im Spitzencluster it’s OWL die Entwicklung intelligenter Verfahren und Systeme, um auch unter variablen Produktionsbedingungen eine zuverlässige Massenfertigung von Kupferbondverbindungen sicherzustellen.Dabei wird der gesamte Prozess der Ultraschall-Verbindungsbildung modelliert. Dies beinhaltet u. a. ein Reibmodell mit gekoppeltem Anbindungsmodell, den Ultraschall-Erweichungseffekt und den Verschleiß des Bondwerkzeugs. Zudem wird das Konzept einer selbstoptimierenden Bondmaschine vorgestellt, welche Prozessparameter in Abhängigkeit von Störgrößen wie Verschleiß anpasst.Das Ultraschallbonden mit Aluminiumdraht ist ein etabliertes Fertigungsverfahren zur Kontaktierung von Leistungshalbleitern. Zukünftige Leistungshalbleiterchips erfordern jedoch einen Technologiewechsel zu Kupferdraht. Die Prozessparameter unterscheiden sich dabei deutlich von den bekannten Aluminiumprozessen, ihre Wechselwirkungen sind weitestgehend unbekannt.
Keywords: Abschlussbericht zum Spitzenclusterprojekt InCuB

Optimization-based reliability control of mechatronic systems - Meyer, Tobias
Reliability-adaptive systems allow an adaptation of system behavior based on current system reliability. They can extend their lifetime at the cost of lowered performance or vice versa. This can be used to adapt failure behavior according to a maintenance plan, thus increasing availability while using up system capability fully. To facilitate setup, a control algorithm independent of a degradation model is desired. A closed loop control technique for reliability based on a health index, a measure for system degradation, is introduced. It uses self-optimization as means to implement behavior adaptation. This is based on selecting the priorities of objectives that the system pursues. Possible working points are computed beforehand using model-based multiobjective optimization techniques. The controller selects the priorities of objectives and this way balances reliability and performance. As exemplary application, an automatically actuated single plate dry clutch is introduced. The entire reliability control is setup and lifetime experiments are conducted. Results show that the variance of time to failure is reduced greatly, making the failure behavior more predictable. At the same time, the desired usable lifetime can be extended at the cost of system performance to allow for changed maintenance intervals. Together, these possibilities allow for greater system usage and better planning of maintenance.
Keywords: dependability; reliability; behavior adaptation; self-optimization; multiobjective optimization; optimal control; automotive drivetrain; clutch system; reliability-adaptive system

Numerical and statistical investigation of weld formation in a novel two-dimensional copper-copper bonding process - Dymel, Collin; Eichwald, Paul; Schemmel, Reinhard; Hemsel, Tobias; Brökelmann, Michael; Hunstig, Matthias; Sextro, Walter ((Proceedings of 7th Electronics System-Integration Technology Conference, Dresden, Germany))
State-of-the-art industrial compact high power electronic packages require copper-copper interconnections with larger cross sections made by ultrasonic bonding. In comparison to aluminium-copper, copper-copper interconnections require increased normal forces and ultrasonic power, which might lead to substrate damage due to increased mechanical stresses. One option to raise friction energy without increasing vibration amplitude between wire and substrate or bonding force is the use of two-dimensional vibration. The first part of this contribution reports on the development of a novel bonding system that executes two-dimensional vibrations of a tool-tip to bond a nail- like pin onto a copper substrate. Since intermetallic bonds only form properly when surfaces are clean, oxide free and activated, the geometries of tool-tip and pin were optimised using finite element analysis. To maximize the area of the bonded annulus the distribution of normal pressure was optimized by varying the convexity of the bottom side of the pin. Second, a statistical model obtained from an experimental parameter study shows the influence of different bonding parameters on the bond result. To find bonding parameters with the minimum number of tests, the experiments have been planned using a D-optimal experimental design approach.
Keywords: ultrasonic wire-bonding; bond-tool design; parameter identification; statistical engineering

Experimental investigations on the impact of bond process parameters in two-dimensional ultrasonic copper bonding - Dymel, Collin; Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias ((Proceedings of 8th Electronics IEEE CPMT Symposium Japan (ICSJ 2018), Kyoto, Japan))
Ultrasonic bonding and welding are common friction based approaches in the assembly of power electronics. Interconnections with cross-sections of 0.3 mm² up to 12 mm² made from copper are well suited in high power applications. For increasing friction energy, which is responsible for bond formation, a two-dimensional vibration approach is applied to newly developed interconnection pins. Using two-dimensional vibration for bonding requires identification of suitable bonding parameters. Even though simulation models of wire bonding processes exist, parameters for the two-dimensional pin-bonding process cannot be derived accurately yet. Within this contribution, a methodology and workflow for experimental studies identifying a suitable bond parameter space are presented. The results of a pre-study are used to set up an extensive statistical parameter study, which gives insights about the bond strength change due to bond process parameter variation. By evaluation of electrical data captured during bonding, errors biasing the resulting shear forces are identified. All data obtained during the experimental study is used to build a statistical regression model suitable for predicting shear forces. The accuracy of the regression model’s predictions is determined and the applicability to predict process parameters or validate simulation models is assessed. Finally, the influence of the tool trajectory on the bond formation is determined, comparing one dimensional, elliptic and circular trajectories.
Keywords: ultrasonic two-dimensional bonding; electrical interconnection; process parameters

Effects of different working frequencies on the joint formation in copper wire bonding - Schemmel, Reinhard; Althoff, Simon; Sextro, Walter; Unger, Andreas; Brökelmann, Michael; Hunstig, Matthias (CIPS 2018 - 10th International Conference on Integrated Power Electronics Systems (CIPS 2018))
Ultrasonic wire bonding is used to connect the electrical terminals of semiconductor modules in power electronics. Mul- tiple inﬂuencing factors in wedge/wedge bonding are known and extensively investigated. A constructively settable but rarely examined parameter is the bonding frequency. In case of bonding on challenging substrates, e.g. supple substruc- tures, a high inﬂuence of the working frequency is observed. The choice of the working frequency is typically based on experimental investigations for a certain component or substrate and needs to be evaluated anew for new applications. A profound understanding of the inﬂuence of the working frequency is required to achieve a reliable bond process and a short process development. Here a generalized model for the numerical simulation of the bond formation with respect to the dynamics of the substructure is presented. The simulation results are compared to experiments using 300 µm copper wire at different working frequencies and geometries of the substructure.

Intelligent Production of Wire Bonds using Multi-Objective Optimization – Insights, Opportunities and Challenges - Unger, Andreas; Hunstig, Matthias; Meyer, Tobias; Brökelmann, Michael; Sextro, Walter (In Proceedings of IMAPS 2018 – 51st Symposium on Microelectronics, Pasadena, CA, 2018)
Ultrasonic wire bonding is an indispensable process in the industrial manufacturing of semiconductor devices. Copper wire is increasingly replacing the well-established aluminium wire because of its superior electrical, thermal and mechanical properties. Copper wire processes differ significantly from aluminium processes and are more sensitive to disturbances, which reduces the range of parameter values suitable for a stable process. Disturbances can be compensated by an adaption of process parameters, but finding suitable parameters manually is difficult and time-consuming. This paper presents a physical model of the ultrasonic wire bonding process including the friction contact between tool and wire. This model yields novel insights into the process. A prototype of a multi-objective optimizing bonding machine (MOBM) is presented. It uses multi-objective optimization, based on the complete process model, to automatically select the best operating point as a compromise of concurrent objectives.
Keywords: wire bonding; multi-objective optimization; process model; copper wire; self-optimization

A particle filtering approach for temperature based prognostics - Bender, Amelie; Sextro, Walter (Safety and Reliability – Safe Societies in a Changing World)
Rubber-metal-elements are used in a wide range of applications for vibration and sound isola- tion. Nowadays it is state of the art to calculate the lifetimes of these elements under mechanical stress prior to their service life. To establish more reliable and safer rubber-metal-elements, continuous monitoring by dif- ferent sensors can be used. Especially prognostics enable a rise in reliability, availability and safety. To estab- lish these advantages, estimating the remaining useful lifetime of rubber-metal-elements should be realized during its service life based on current information on its condition. Therefore a suitable measure to monitor the condition of the element is necessary. This work focuses on temperature signals. This approach allows in- cluding the ambient temperature and thereby involving changing operating conditions. For estimating the RUL of rubber-metal-elements a model-based prognostics approach based on particle filtering is proposed. Its performance is analyzed regarding relevant parameters to enable the best performance for the applied data.

Numerical and experimental investigations in ultrasonic heavy wire bonding - Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter (6th European Conference on Computational Mechanics (ECCM 6))
Ultrasonic wedge/wedge-wire bonding is used to connect electrical terminals of semiconductor modules in power electronics. The wire is clamped with a tool by a normal force and ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes contaminations like oxide layers are removed from the contact zone and the surface roughness is reduced, thus the real contact area is increased. In the next step of bond formation, thermomechanical forces create micro-junctions between the wire and substrate and the bond strength increases. The bond parameters like the bond normal force, the ultrasonic vibration amplitude and the geometry of the clamping tool show a high influence on the strength and reliability of the wire bond and need to be investigated in detail. Therefore, in this contribution the dynamical behaviour of the ultrasonic system, the wire and the substrate are modeled in form of substructures, which are connected by the friction contacts between tool and wire and between wire and substrate. Approaches for modelling the time variant contact behaviour, the substrate dynamics, and the model order reduction for a time efficient simulation are described to simulate the full bonding process.

Vibration Assisted Dosing, Mixing and Transport of Dry Fine Powders - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter.; Sextro, Walter (ACTUATOR 2018; 16th International Conference on New Actuators)
The handling of fine powders is an important task in modern production processes. However, as fine powders strongly tend to adhesion and agglomeration, their processing with conventional methods is difficult or impossible. Especially when processing small amounts of highly sensitive fine powders, conventional methods reach their technical limits. In process steps such as dosing, transport, and especially mixing of fine powders new methods are required. Apart from the well-known method of manipulating powder properties by adding chemical additives, this contribution aims at improving the handling of dry fine powders by using vibrations at different frequencies. Modules are presented, which enable the continuous dosing, the homogeneous mixing and the transport of dry fine powders. Finally, these modules are combined for the production of a homogeneous mixture of two dry fine powders.

Vibration-Assisted Handling of Dry Fine Powders - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Sextro, Walter (Actuators 2018, 7(2).)
Abstract:Since ﬁne powders tend strongly to adhesion and agglomeration, their processing withconventional methods is difﬁcult or impossible. Typically, in order to enable the handling of ﬁnepowders, chemicals are added to increase the ﬂowability and reduce adhesion. This contributionshows that instead of additives also vibrations can be used to increase the ﬂowability, to reduceadhesion and cohesion, and thus to enable or improve processes such as precision dosing, mixing,and transport of very ﬁne powders. The methods for manipulating powder properties are describedin detail and prototypes for experimental studies are presented. It is shown that the handling of ﬁnepowders can be improved by using low-frequency, high-frequency or a combination of low- andhigh-frequency vibration.
Keywords: powder handling; ﬂowability; dosing; transport; mixing; dispersion; piezoelectricactuators; vibrations

Steigerung der Intelligenz mechatronischer Systeme - Meyer, Tobias; Kaul, Thorben; Kimotho, James Kuria; Sextro, Walter
Selbstoptimierung bietet die Möglichkeit der autonomen Anpassung des Systemverhaltens an veränderliche Ziele. Dabei ist vor allem der Aspekt Zuverlässigkeit von maßgeblicher Bedeutung, da über einen an die aktuelle Systemzuverlässigkeit angepassten Betriebspunkt die Leistungsfähigkeit verbessert wird, während das Ausfallverhalten besser vorhersehbar wird. Zur Anpassung des Systemverhaltens an die aktuelle Zuverlässigkeit mittels Selbstoptimierung müssen die ersten beiden Schritte des Selbstoptimierungsprozesses unterstützt werden. Für die Analyse der Ist-Situation ist eine Erkennung des aktuellen Degradationszustands mittels Condition Monitoring notwendig. Zur Auswahl geeigneter Verfahren werden bestehende Ansätze hinsichtlich ihrer Eignung klassifiziert. Der zweite Schritt, die Bestimmung der Systemziele, wird durch eine strukturierte Methode zum Finden verlässlichkeitsrelevanter Zielfunktionen ergänzt. Dabei werden kritische Komponenten identifiziert, Optimierungsparameter festgelegt und die Verlässlichkeit in Abhängigkeit des Systemverhaltens quantifiziert. Entwickler selbstoptimierender Systeme werden somit durch geeignete Mittel bei der Implementierung beider Schritte unterstützt. Abschließend wird der praktische Einsatz der vorgestellten Methoden anhand zweier Beispiele gezeigt.

Multiskalen-Kontaktmodellierung unter Berücksichtigung der Rauigkeit und fluiden Zwischenschichten am Beispiel des Rad-Schiene-Kontakts - Neuhaus, Jan
Keywords: Kontaktmodellierung; Rauigkeit

Modellbasierte Mehrzieloptimierung zur Herstellung von Ultraschall-Drahtbondverbindungen in Leistungshalbleitermodulen - Unger, Andreas
Das Ultraschall-Drahtbonden mit Aluminiumdraht ist aktuell ein Standardverfahren zur Kontaktierung von Leistungshalbleitermodulen. Jedoch soll die Einführung von Kupferdraht als Bondmaterial in der Zukunft zu zahlreichen Verbesserungen der Module führen. Dies ist bedingt durch die wesentlich besseren elektrischen und thermischen Eigenschaften von Kupfer gegenüber Aluminium, die dazu führen, dass z. B. eine weitere Miniaturisierung elektrischer Komponenten möglich wird. Darüber hinaus könnte insbesondere die Verlässlichkeit der Module signifikant verbessert werden. Doch bisher wurde Kupferdraht trotz seiner überlegenen physikalischen Eigenschaften im Wesentlichen nur vereinzelt eingesetzt, da der Prozess deutlich empfindlicher auf Störgrößen reagiert. Um dennoch zuverlässige Kupferbondverbindungen in Leistungshalbleitermodulen herstellen zu können, wird in dieser Arbeit ein Verfahren vorgestellt, das die Herstellung von Ultraschall-Bondverbindungen mittels modellbasierter Mehrzieloptimierung realisiert. Dazu ist umfangreiches Prozesswissen in Form eines geeigneten Modells für den Bondprozess notwendig. Das vorgestellte Modell ist in der Lage, alle notwendigen Effekte und den Einfluss wesentlicher Prozessparameter detailliert abzubilden, sodass eine anschließende Mehrzieloptimierung zur Bestimmung der pareto-optimalen Betriebspunkte und zugehörigen Prozessparameter ermöglicht wird. Die dafür notwendigen Teilmodelle und Mehrzieloptimierungen werden dargestellt und validiert. Überdies wird ein Prototyp in Form einer modifizierten Bondmaschine inklusive einer Möglichkeit zur Verhaltensanpassung aufgebaut und getestet.
Keywords: Drahtbondverbindungen

Multi-dimensional Ultrasonic Copper Bonding – New Challenges for Tool Design - Eichwald, Paul; Althoff, Simon; Schemmel, Reinhard; Sextro, Walter; Unger, Andreas; Brökelmann, Michael; Hunstig, Matthias (IMAPSource)
In power electronics, copper connector pins are e.g. used to connect control boards with power modules. The new chip generation based on SiC and GaN technology increase the power density of semiconductor modules significantly with junction temperatures reaching 200°C. To enable reliable operation at such high temperature, the soldering of these connector pins should be substituted by a multi-dimensional copper-copper bonding technology. A copper pin welded directly on DBC substrate also simplifies the assembly. With this aim, a proper bond tool and a suitable connector pin geometry are designed. This paper presents a two-dimensional trajectory approach for ultrasonic bonding of copper pieces, e.g. connector pins, with the intention to minimize mechanical stresses exposed to the substrate. This is achieved using a multi-dimensional vibration system with multiple transducers known from flip chip bonding. Applying a planar relative motion between the bonding piece and the substrate increases the induced frictional power compared to one-dimensional excitation. The core of this work is the development of a new tool design which enables a reliable and effective transmission of the multidimensional vibration into the contact area between nail-shaped bonding piece and substrate. For this purpose, different bonding tool as well as bonding piece designs are discussed. A proper bonding tool design is selected based on the simulated alternatives. This tool is examined in bonding experiments and the results are presented. In addition, different grades of hardness for bonding piece and substrate are examined as well as different bonding parameters. Optical inspection of the bonded area shows the emergence of initial micro welds in form of a ring which is growing in direction of the interface boundaries with increasing bonding duration.
Keywords: International Symposium on Microelectronics

Entwicklung verlässlicher, intelligenter Systeme - Sextro, Walter; Meyer, Tobias; Kaul, Thorben; Kimotho, James Kuria (VDI-Berichte 2307–28. Tagung Technische Zuverlässigkeit (TTZ 2017) - Entwicklung und Betrieb zuverlässiger Produkte.)
Intelligente technische Systeme sind durch einen erhöhten Funktionsumfang charakterisiert, der diese dazu befähigt, autonom auf wechselnde Umgebungsbedingungen, Anforderungen und inhärente Systemzustände zu reagieren. Dies kann mit den Methoden der Selbstoptimie-rung erreicht werden. Hier werden mit Verfahren der Mehrzieloptimierung mögliche Betriebs-punkte des Systems bestimmt zwischen denen das System im Betrieb autonom auswählt und somit eine Verhaltensadaption erwirkt. Zur Berechnung der Betriebspunkte ist es notwendig ein Modell des Systemverhaltens aufzustellen und das Verhalten hinsichtlich verschiedener, meist konfliktärer, Ziele zu quantifizieren. Bei der Modellierung des Systemverhaltens und der Formulierung der Ziele stellt die Absiche-rung der Verlässlichkeit auf Grund der zunehmenden Systemkomplexität eine große Heraus-forderung dar, der im Entwicklungsprozess begegnet werden muss. Die Implementierung von Selbstoptimierung bietet darüber hinaus in Kombination mit einer Zustandsüberwachung im Betrieb die Möglichkeit einer zuverlässigkeitsbasierten Verhaltensanpassung, deren Potential zu einer Steigerung der Verlässlichkeit genutzt werden kann. In dieser Arbeit werden die Entwicklung intelligenter technischer Systeme und die damit ver-bundenen notwendigen Entwicklungsschritte zur Absicherung der Verlässlichkeit anhand von selbstoptimierenden Systemen betrachtet. Dazu gehören die Formulierung verlässlichkeitsre-levanter Ziele und die Implementierung einer Zustandsüberwachung als Basis für eine zuver-lässigkeitsbasierte Verhaltensanpassung. Es werden auf Grundlage einer Beschreibung der Entwicklungsschritte, Potentiale zur Steigerung der Verlässlichkeit sowie Chancen und zukünf-tige Herausforderungen herausgestellt und diskutiert.
Keywords: intelligente Systeme

Integrated modeling og behavior and reliability in system development - Hentze, Julian; Kaul, Thorben; Grässler, Iris; Sextro, Walter (ICED17, 21st International conference on enginieering design)
The integrated modeling of behavior and reliability in system development delivers a model-based approach for reliability investigation by taking into account the dynamic system behavior as well as the system architecture at different phases of the development process. This approach features an automated synthesis of a reliability model out of a behavior model enabling for the closed loop modeling of degradation of the system and its (dynamic) behavior. The approach is integrated into the development process following Systems Engineering. It is based on standard models used in model-based development methodologies i.e. SysML or Matlab/Simulink. In addition to the theoretical description of the necessary steps the procedure is validated by an application example at two stages of the development process.
Keywords: Design for X (DfX); Product modelling / models; Robust design; Systems Engineering (SE); Reliability

Entwicklung eines Condition Monitoring Systems für Gummi-Metall-Elemente - Bender, Amelie; Kaul, Thorben; Sextro, Walter (Verlagsschriftenreihe des Heinz Nixdorf Instituts Band 369, Paderborn, 2017)
Zuverlässigkeit, Sicherheit und Verfügbarkeit gewinnen bei der Anwendung von technischen Systemen eine immer größere Bedeutung. Aus diesem Grund hat sich Condition Monitoring, die Zustandsüberwachung eines technischen Produkts, in verschiedenen Industriebranchen etabliert. Die sensorbasierte Überwachung eines Produkts während seiner Betriebsdauer in Kombination mit Condition Monitoring Methoden ermöglichen die Bestimmung des aktuellen Zustands des Produkts und somit eine Diagnose, ob das Produkt seine ihm zugeschriebene Funktion zum aktuellen Zeitpunkt erfüllt. Neben Diagnosen bietet Condition Monitoring auch die Möglichkeit Prognosen aufzustellen, dabei wird die restliche Nutzungsdauer des Produkts aufbauend auf geeigneten Sensordaten geschätzt. So kann eine intelligente Wartungsplanung umgesetzt werden, die im Gegensatz zu klassischen Ansätzen keine festen Wartungsintervalle benötigt und die Nachteile einer rein reaktiven Wartung kompensiert. Stattdessen ist es möglich ein Element bis vor das Ende seiner Lebensdauer zu nutzen und erst dann zu warten, um eine optimale Nutzung zu gewährleisten. Durch eine Bestimmung der verbleibenden Restlebensdauer während des Betriebs ist eine optimale Wartungsplanung möglich, wodurch die Verfügbarkeit und die Auslastung der überwachten Produkte signifikant gesteigert werden kann. In dieser Arbeit soll ein produktspezifisches Condition Monitoring System für Gummi-Metall-Elemente entwickelt werden. Diese Elemente werden zur Federung, Geräusch- und/oder Schwingungsisolation in vielen verschiedenen Anwendungen eingesetzt, wie bspw. in Nutz- und Schienenfahrzeugen oder Windenergieanlagen. In Industrie und Forschung werden bereits Zustandsüberwachungen von Systemen mit integrierten Gummi-Metall-Elementen eingesetzt, allerdings noch keine Condition Monitoring Systeme zur alleinigen Zustandsüberwachung dieser Elemente. Aktuell ist es üblich die Lebensdauer dieser Elemente aufbauend auf beschleunigten Lebensdauerversuchen und Erfahrungswerten abzuschätzen. Mit dem Ziel die Lebensdauer des fokussierten Produkts präziser vorherzusagen und damit eine intelligente Wartungsplanung zu ermöglichen, wird die Entwicklung eines Condition Monitoring Systems für Gummi-Metall-Elemente angestrebt und in dieser Arbeit erläutert.
Keywords: Zustandsüberwachung; Condition Monitoring; Prognose; Gummi-Metall-Elemente; Restlebensdauerschätzung

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

Analysis of pipe vibration in an ultrasonic powder transportationsystem - Dunst, Paul; Hemsel, Tobias; Sextro, Walter (elsevier)
The transportation of dry fine powders is an emerging technologic task, as in biotechnology, pharmaceu-tical and coatings industry the particle sizes of processed powders get smaller and smaller. Fine powdersare primarily defined by the fact that adhesive and cohesive forces outweigh the weight forces, leadingto mostly unwanted agglomeration (clumping) and adhesion to surfaces. Thereby it gets more difficult touse conventional conveyor systems (e.g. pneumatic or vibratory conveyors) for transport. A rather newmethod for transporting these fine powders is based on ultrasonic vibrations, which are used to reducefriction between powder and substrate. Within this contribution an experimental set-up consisting of apipe, a solenoid actuator for axial vibration and an annular piezoelectric actuator for the high frequencyradial vibration of the pipe is described. Since amplitudes of the radial pipe vibration should be as large aspossible to get high effects of friction reduction, the pipe is excited to vibrate in resonance. To determinethe optimum excitation frequency and actuator position the vibration modes and resonance frequenciesof the pipe are calculated and measured. Results are in good accordance.
Keywords: Powder transport Piezoelectrics Ultrasonics Pipe vibration Finite element simulation Fine powder

Formulation of reliability-related objective functions for design of intelligent mechatronic systems - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (SAGE Journals)
State-of-the-art mechatronic systems offer inherent intelligence that enables them to autonomously adapt their behavior to current environmental conditions and to their own system state. This autonomous behavior adaptation is made possible by software in combination with complex sensor and actuator systems and by sophisticated information processing, all of which make these systems increasingly complex. This increasing complexity makes the design process a challenging task and brings new complex possibilities for operation and maintenance. However, with the risk of increased system complexity also comes the chance to adapt system behavior based on current reliability, which in turn increases reliability. The development of such an adaption strategy requires appropriate methods to evaluate reliability based on currently selected system behavior. A common approach to implement such adaptivity is to base system behavior on different working points that are obtained using multiobjective optimization. During operation, selection among these allows a changed operating strategy. To allow for multiobjective optimization, an accurate system model including system reliability is required. This model is repeatedly evaluated by the optimization algorithm. At present, modeling of system reliability and synchronization of the models of behavior and reliability is a laborious manual task and thus very error-prone. Since system behavior is crucial for system reliability, an integrated model is introduced that integrates system behavior and system reliability. The proposed approach is used to formulate reliability-related objective functions for a clutch test rig that are used to compute feasible working points using multiobjective optimization.
Keywords: Integrated model; reliability; system behavior; Bayesian network; multiobjective optimization

Piezoelectric Inertia Motors—A Critical Review of History, Concepts, Design, Applications, and Perspectives. - Hunstig, Matthias (Actuators. 2017, 6(1)-7.)
Piezoelectric inertia motors also known as stick-slip motors or (smooth) impact drives use the inertia of a body to drive it in small steps by means of an uninterrupted friction contact. In addition to the typical advantages of piezoelectric motors, they are especially suited for miniaturisation due to their simple structure and inherent fine-positioning capability. Originally developed for positioning in microscopy in the 1980s, they have nowadays also found application in mass-produced consumer goods. Recent research results are likely to enable more applications of piezoelectric inertia motors in the future. This contribution gives a critical overview of their historical development, functional principles, and related terminology. The most relevant aspects regarding their design i.e., friction contact, solid state actuator, and electrical excitation are discussed, including aspects of control and simulation. The article closes with an outlook on possible future developments and research perspectives.

Model based optimization of dynamics in adaptive headlamps - Schulze, Sebastian; Sextro, Walter; Kister, K. (Proceedings of the 12th International Symposium on Automotive Lighting 2017)

MoRFUS: Mobile Reinigungseinheit für Förderketten basierend auf Ultraschall - Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter (43. Deutsche Jahrestagung für Akustik)
ln der industriellen Fertigung werden zum Transport von Bauteilen häufig Förderketten genutzt. Obwohl die Förderketten meist nicht direkt mit den Arbeitsmedien in Berührung kommen, werden sie indirekt durch vagabundierende Stäube und Pulver, die an der geölten Kette anhaften, im Laufe der Zeit stark verschmutzt. Ein derart im Betrieb verschmutztes Kettenglied ist in Abbildung 1 dargestellt. Um die Lebensdauer der Ketten zu erhöhen und das Herunterfallen von Schmutzpartikel auf die Produkte zu vermeiden, muss die Kette regelmäßig gereinigt werden. Ziel des hier beschriebenen Forschungsvorhabens ist die Entwicklung eines Systems, das in der Lage ist, ein einzelnes Kettenglied in unter 60 s mittels Ultraschall zu reinigen. In [1] wurde in ersten Versuchen nachgewiesen, dass Stabschwinger in Abhängigkeit des Sonotrodenabstands zum Reinigungsobjekt und der Ultraschallamplitude eine intensive Reinigungswirkung entfalten. Das Konzept der Reinigungsanlage sieht deshalb vor, im ersten Schritt die stark verschmutzten Kettenglieder durch ein hochintensives Kavitationsfeld von direkt eingetauchten Stabschwingern vorzureinigen und anschließend schwer zugängliche Be- reiche wie Hinterschneidungen oder Bohrungen mittels konventioneller Tauchschwinger von Verschmutzungen zu befreien. Für den Stabschwinger wird die sogenannte - Sonotrode untersucht; diese wird unter anderem auch in der Sonochemie verwendet. Ein wesentliches Merkmal der Sonotrode ist eine hohe Amplitudenübersetzung bei einer gleichzeitig großen Abstrahlfläche. Neben dem Entwurf mittels der L /2 -Synthese wird die Reinigungswirkung der Sonotrode in Abhängigkeit der Ultraschallamplitude und dem Abstand zum Reinigungsobjekt in einer Versuchsreihe untersucht. Zur genaueren Betrachtung der Reinigungs- mechanismen eines Stabschwingers werden abschließend Hochgeschwindigkeitsaufnahmen vorgestellt und analysieren.
Keywords: wire bonding; dynamic behavior; modeling

Neuartiges Konzept zur Lebensdauerprognose von Gummi-Metall-Elementen - Bender, Amelie; Sextro, Walter; Reinke, Kai (VDI-Berichte 2301)
In der Windenergieindustrie haben die Größen Zuverlässigkeit, Sicherheit und Verfügbarkeit eine enorme Bedeutung erlangt aufgrund des Trends Windenergieanlagen zur optimalen Windausnutzung an schwer zugänglichen Positionen aufzustellen, wie bspw. Offshore. Dies führt zu erschwerten Wartungsbedingungen und damit zu höheren Kosten. Der Einsatz von Condition Monitoring hat sich in dieser Industrie etabliert, denn diese Technik ermöglicht eine Zustandsdiagnose des überwachten Systems und eine Prognose seiner nutzbaren Restlebensdauer (remaining useful life: RUL), jeweils basierend auf geeigneten Sensordaten. In dieser Arbeit wird ein Konzept für ein produktspezifisches Condition-Monitoring-System für Gummi-Metall-Elemente (GM-Elemente) vorgestellt, welches den Schwerpunkt auf die Prognose der RUL dieser Elemente setzt. In Windenergieanlagen werden zahlreiche GM-Elemente zur Geräusch- und Schwingungsisolation verwendet. Der Einsatz des hier vorgestellten produktspezifischen Condition-Monitoring-Systems kann somit einen erheblichen Beitrag zum verlässlichen Betrieb von Windenergieanlagen liefern, da die Überwachung einzelner Komponenten in die Zustandsüberwachung der gesamten Anlage integriert und dadurch der Betrieb der Anlage optimiert werden kann. In dieser Arbeit werden einige Herausforderungen diskutiert, die sich bei der Entwicklung eines Condition-Monitoring-Systems für GM-Elemente ergeben. So wird evaluiert, welche Größen sich zur Beschreibung der Alterung eines spezifischen Elements eignen und wie diese gemessen werden können. Temperaturen werden bereits in einigen technischen Systemen, wie auch in Windenergieanlagen, aufgezeichnet und ausgewertet, aber ihr Potential für die Bestimmung der RUL der überwachten Komponente ist noch nicht ausgeschöpft. Hier wird eine Lösungsmöglichkeit vorgestellt, die auf Temperatursensoren aufbaut. Als Grundlage für die Entwicklung des Condition-Monitoring-Systems wurden beschleunigte Lebensdauerversuche der GM-Elemente auf einem Versuchsstand zur Schwingungsanalyse durchgeführt. In diesen Lebensdauerversuchen wird die mechanische Alterung eines GM-Elements über einen kraftgeregelten Hydraulikzylinder erzielt. Dabei wird das Ende der Lebensdauerversuche in einem ersten Schritt über die Wegamplitude des Zylinders bestimmt. Während dieser Versuche wurden diverse Sensoren eingesetzt. Die aufgezeichneten Temperaturdaten zeigen, dass sich Temperaturmessungen eignen die Lebensdauer von GM-Elementen mittels Condition Monitoring Prognosemethoden zu schätzen.

Modellbasierte Prognose der nutzbaren Restlebensdauer von Gummi-Metall-Elementen - Bender, Amelie; Kimotho, James Kuria; Kohl, Sergej; Sextro, Walter; Reinke, Kai (15. Internationale Schienenfahrzeugtagung)
In vielen verschiedenen Industriezweigen hat sich Condition Monitoring aufgrund seiner finanziellen und sicherheitstechnischen Vorteile bereits etabliert. Um die Verlässlichkeit und die Auslastung zu steigern, sowie um die Lebenszykluskosten zu reduzieren, steigt auch im Schienenfahrzeugbereich die Anzahl an eingesetzten Condition Monitoring Systemen. Studien zu Versagensmodi von Schienenfahrzeugen haben gezeigt, dass Versagensursachen meistens in den Radprofilen oder im Fahrwerk liegen [1]. Wird das Fahrwerk heute mittels Condition Monitoring überwacht, werden hierfür häufig Sensoren an den Wagons angebracht, um bspw. deren Schwingungen zu kontrollieren [2, 3]. In dieser Arbeit liegt der Fokus auf Gummi-Metall-Elementen (GM-Elementen) der Jörn GmbH.; als elastische Lager im Drehgestell sind diese Teil des Fahrwerks eines Schienenfahrzeugs. Mit dem Ziel die Wartungsplanung dieser Elemente zu optimieren, ist untersucht worden, ob diese Elemente einzeln mittels Condition Monitoring überwacht werden können. Die hierfür durchgeführten beschleunigten Lebensdauertests werden im nächsten Abschnitt erläutert. Anschließend werden die modellbasierten Methoden dargestellt, die aufbauend auf den im Versuch aufgezeichneten Daten eine Prognose der nutzbaren Restlebensdauer (RUL, remaining useful lifetime) der GM-Elemente aufstellen. Im letzten Abschnitt folgen eine kurze Zusammenfassung und ein Ausblick.

Development and Performance Evaluation of Prognostic Approaches for Technical Systems - Kimotho, James Kuria
As the need to improve reliability, availability and safety of technical systems increases, a large number of proactive maintenance strategies have been proposed. Of greater interest is the development of prognostic and health management strategies where maintenance is scheduled based on the current and the predicted future health state of a technical system. In addition, prognostic information can be used to control the reliability of intelligent mechatronic systems to ensure their mission objective is achieved. Therefore methodologies for estimating these current and future health states reliably and accurately are imperative. With the advancement in sensor technology, majority of the present day technical systems are installed with a network of sensors for condition or performance monitoring. This has led to the increased application of machine learning algorithms in condition monitoring. Depending on the sensor data available, different approaches for utilizing the data with machine learning algorithms can be applied. However, aguide for selecting the appropriate approach for a given system is either lacking or has not been explored extensively. Therefore, this work aims at providing a guide for selecting suitable approaches and machine learning algorithms for a given system depending on the available sensor data.Five approaches for prognostics and an ensemble of the best performing approaches are presented. Since the performance of machine learning algorithms is highly dependent on the input features, methods for feature extraction and selection are also presented. The approaches are evaluated and validated with run-to-failure condition monitoring data of actual systems. This information could serve as a guide for selecting the appropriate method for a given kind of system depending on the available condition monitoring data.

Micro Wear Modeling in Copper Wire Wedge Bonding - Eichwald, Paul; Unger, Andreas; Eacock, Florian; Althoff, Simon; Sextro, Walter; Guth, Karsten; Brökelmann, Michael (IEEE CPMT Symposium Japan, 2016)
Ultrasonic wire bonding is a common technology for connecting electrodes of electronic components like power modules. Nowadays, bond connections are often made of copper instead of aluminum due to its thermal and mechanical assets. One of the main cost factors in the wire bonding process is the acquisition cost of consumables such as bonding tools. For copper wire bonding tool lifetime is much lower than for aluminium bonding. This paper presents a micro wear model for wedge/wedge bonding tools that was validated by observing wear patterns with a scanning electron microscope. The wear coefficient is determined in long-term bonding tests. The application of Fleischer´s wear approach incorporating frictional power to a finite element simulation of the bonding processes is used to shift element nodes depending on the rising frictional power for finite element modeling. The presented simulation method can be used to take tool wear into consideration for creating tools with increased lifetime. This enables the production of reliable bond connections using heavy as well as thin wire of any material. The paper discusses the predominant influences of wear on the main tool functions and their changes over tool life. Furthermore, the influence of the tool groove angle on the tool wear was investigated. One of the main results is that the wear is largest during the last phase of each bonding process, when the contact area between tool and wire is largest.

Reliable Manufacturing of Heavy Copper Wire Bonds Using Online Parameter Adaptation - Meyer , Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Usage of copper wire bonds allows to push power boundaries imposed by aluminum wire bonds. Copper allows higher electrical, thermal and mechanical loads than aluminum, which currently is the most commonly used material in heavy wire bonding. This is the main driving factor for increased usage of copper in high power applications such as wind turbines, locomotives or electric vehicles. At the same time, usage of copper also increases tool wear and reduces the range of parameter values for a stable process, making the process more challenging. To overcome these drawbacks, parameter adaptation at runtime using self-optimization is desired. A self-optimizing system is based on system objectives that evaluate and quantify system performance. System parameters can be changed at runtime such that pre-selected objective values are reached. For adaptation of bond process parameters, model-based self-optimization is employed. Since it is based on a model of the system, the bond process was modeled. In addition to static model parameters such as wire and substrate material properties and vibration characteristics of transducer and tool, variable model inputs are process parameters. Main simulation result is bonded area in the wiresubstrate contact. This model is then used to find valid and optimal working points before operation. The working point is composed of normal force and ultrasonic voltage trajectories, which are usually determined experimentally. Instead, multiobjective optimalization is used to compute trajectories that simultaneously optimize bond quality, process duration, tool wear and probability of tool-substrate contacts. The values of these objectives are computed using the process model. At runtime, selection among pre-determined optimal working points is sufficient to prioritize individual objectives. This way, the computationally expensive process of numerically solving a multiobjective optimal control problem and the demanding high speed bonding process are separated. To evaluate to what extent the pre-defined goals of self-optimization are met, an offthe- shelf heavy wire bonding machine was modified to allow for parameter adaptation and for transmitting of measurement data at runtime. This data is received by an external computer system and evaluated to select a new working point. Then, new process parameters are sent to the modified bonding machine for use for subsequent bonds. With these components, a full self-optimizing system has been implemented.
Keywords: Self-optimization; adaptive system; bond process; copper wire

Validated Simulation of the Ultrasonic Wire Bonding Process - Unger, Andreas; Schemmel, Reinhard; Meyer, Tobias; Eacock, Florian; Eichwald, Paul; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (Wear Modeling in Copper Wire Wedge Bonding. IEEE CPMT Symposium Japan, 2016)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tooltip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard’s wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.
Keywords: the Ultrasonic Wire Bonding Process

Shape-Dependent Transmittable Tangential Force of Wire Bond Tools - Althoff, Simon; Meyer, Tobias; Unger, Andreas; Sextro, Walter; Eacock, Florian (IEEE 66th Electronic Components and Technology Conference)
Wire bonding has been an established packaging technology for decades. When introducing copper as wire material for high power applications, adaptations to the bonding process and to machines became necessary. Here, challenges occur due to the stiffer wire material and changing oxide layers on the contact partners. To achieve sufficient process stability, a clean bond area is required, which can only be achieved with high shear stresses in the contact partners surfaces. These necessitate high normal forces to plastically deform the wire and substrate. To achieve such high stresses in the contact area, the bonding tool needs to be able to transmit the needed tangential forces to the top side of the wire. The wire itself performs a shear movement and transmits the force into the contact area to clean the contaminant and oxide layers and to level the desired bond surfaces. The main function of the tool is to transmit these forces. If the bond tool can only transmit low forces in the direction of excitation, the parameter space for a stable bond process is severely restricted. Here, a modeling approach to estimate how well different tool shapes meet the demand of transmitting high tangential forces is presented. The model depends on wire deformation and thus on the ultrasonic softening effect.
Keywords: finite element simulation; wire bonding; tool geometry

Kupferbondverbindungen intelligent herstellen - Brökelmann, Michael; Unger, Andreas; Meyer, Tobias; Althoff, Simon; Sextro, Walter; Hunstig, Matthias; Biermann, Florian; Guth, Karsten (wt-online)
Leistungshalbleitermodule werden leistungsfähiger, effizienter, kompakter und haltbarer Ziel dieses Innovationsprojekts des Spitzenclusters „it’s OWL – Intelligente Technische Systeme OstWestfalen-Lippe“ ist die Entwicklung von selbstoptimierenden Verfahren, um unter variablen Produktionsbedingungen zuverlässige Kupferbondverbindungen herstellen zu können. Die Ultraschall-Drahtbondmaschine erhält die Fähigkeit, sich automatisch an veränderte Bedingungen anzupassen. Hierzu wird der gesamte Prozess der Ultraschall-Verbindungsbildung modelliert und neueste Verfahren der Selbstoptimierung angewandt. Die Evaluierung erfolgt anhand eines Prototypen in Form einer modifizierten Bondmaschine. Intelligent production of heavy copper wire bonds It is the aim of this innovation-project to develop a self-optimization system for ultrasonic copper wire bonding. It is part of the leading edge cluster “it’s OWL”. The bonding machine will be able to react autonomously to changing boundary conditions to ensure constant and reliable bonding results. For this, the hole bonding process is modeled in great detail and newest self-optimization techniques are utilized. A prototype-system incorporated in a serial machine is used for evaluation.

Modeling of Complex Redundancy in Technical Systems with Bayesian Networks - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (Proceedings of the Third European Conference of the Prognostics and Health Management Society 2016)
Redundancy is a common approach to improve system reliability, availability and safety in technical systems. It is achieved by adding functionally equivalent elements that enable the system to remain operational even though one or more of those elements fail. This paper begins with an overview on the various terminologies and methods for redundancy concepts that can be modeled sufficiently using established reliability analysis methods. However, these approaches yield very complex system models, which limits their applicability. In current research, Bayesian Networks (BNs), especially Dynamic Bayesian Networks (DBNs) have been successfully used for reliability analysis because of their benefits in modeling complex systems and in representing multi-state variables. However, these approaches lack appropriate methods to model all commonly used redundancy concepts. To overcome this limitation, three different modeling approaches based on BNs and DBNs are described in this paper. Addressing those approaches, the benefits and limitations of BNs and DBNs for modeling reliability of redundant technical systems are discussed and evaluated.

Effect of different oxide layers on the ultrasonic copper wire bond process - Eacock, Florian; Unger, Andreas; Eichwald, Paul; Grydin, Olexandr; Hengsbach, Florian; Althoff, Simon; Schaper, Mirko; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Ultrasonic heavy wire bonding is a commonly used technology to conduct electrical devices in power electronics. In order to facilitate powerful solutions combined with an increased efficiency, involving a material change from aluminum to copper wire as conductor material takes place in recent years. Due to the material related properties, copper wire bonding requires significant higher bond processing parameters such as bond force and ultrasonic power compared to aluminum which can lead to damages or a failure of the bonded component. Therefore, a profound knowledge of the processes prevailing during wire bonding is essential to optimize the application of the copper wires and consequently to achieve the demands on quality and reliability. The behavior of different natural surface oxides of aluminum and copper are assumed to be one reason for the deviation in the required bond parameters. Accordingly, the impact of differently pre-treated substrates surfaces on which the bonding is applied were investigated in this study. First, all conditions investigated (as-received, oxidefree, AlOx and the CuOx) were characterized by utilizing scanning electron microscopy, energy dispersive X-ray spectroscopy, focused ion beam microscopy and atomic force microscopy. In addition, hardness tests were performed as well as perthometer measurements. Afterwards, a 500 $μ$ m copper wire was bonded on the generated surfaces investigated. In consideration of the roughness, shear test of various bond times and microscopic images were evaluated. Finally, the results were compared and discussed. Overall, the current study indicates that an Al-oxide layer is beneficial for welding process in Cu wire bonding. On the contrary, the Cu-oxide is detrimental and leads to a delayed welding of the joining parts. Based on the obtained results, it can be expected that due to an ideal set of Al-oxide layers, lower optimal bond parameters can used to reach high bond strength with good reliability properties.
Keywords: Ultrasonic copper wire bonding; Al-oxide; Cuoxide; oxide-free; roughness; morphology

Condition Monitoring of Bearing Damage in Electromechanical Drive Systems by Using Motor Current Signals of Electric Motors: A Benchmark Data Set for Data-Driven Classification - Lessmeier, Christian; Kimotho, James Kuria; Zimmer, Detmar; Sextro, Walter (European Conference of the Prognostics and Health Management Society)
This paper presents a benchmark data set for condition monitoring of rolling bearings in combination with an extensive description of the corresponding bearing damage, the data set generation by experiments and results of datadriven classifications used as a diagnostic method. The diagnostic method uses the motor current signal of an electromechanical drive system for bearing diagnostic. The advantage of this approach in general is that no additional sensors are required, as current measurements can be performed in existing frequency inverters. This will help to reduce the cost of future condition monitoring systems. A particular novelty of the present approach is the monitoring of damage in external bearings which are installed in the drive system but outside the electric motor. Nevertheless, the motor current signal is used as input for the detection of the damage. Moreover, a wide distribution of bearing damage is considered for the benchmark data set. The results of the classifications show that the motor current signal can be used to identify and classify bearing damage within the drive system. However, the classification accuracy is still low compared to classifications based on vibration signals. Further, dependency on properties of those bearing damage that were used for the generation of training data are observed, because training with data of artificially generated and real bearing damages lead to different accuracies. Altogether a verified and systematically generated data set is presented and published online for further research

Using Adequate Reduced Models for Flexible Multibody Systems of Automotive Mechatronic Systems - Schulze, Sebastian; Sextro, Walter; Kohl, Sergej (2nd International Conference on Automotive Innovation and Green Energy Vehicle (AiGEV) Malaysia 2016)
Multibody models of mechatronic systems are usually interdisciplinary and are continuously gaining complexity, due to a growing demand for comprehensive models of systems including effects of electro mechanics, elastic bodies, contacts and friction. To be capable of simulating large models with subassemblies and contact between bodies, reduction techniques are required, which need certain experience in the choice of parameters. This publication discusses different possibilities for the modal description of structures in flexible multibody models with application to an Adaptive Frontlighting System in ADAMS. It will be shown that mode count, assembling of structures before and after modal reduction and influence of damping parameters of particular structures and subassemblies affect the behavior of the entire system. A common reduction technique for flexible structures in multibody models is the component mode synthesis, which uses a certain number of modes for description of the modal behavior of a structure. The influence of the mode count will be shown by means of different modal descriptions of one structure that contributes to a comprehensive model. Another study will prove that modal data of subassemblies and assemblies of modal reduced single structures lead to different models. The definition of damping parameters depends on the number of structures that have been added to an assembly before modal reduction and on the number of modal reduced structures. The comparison of subassemblies and the entire model to experimental data will highlight the accuracy, computational overhead, complexity of models and modeling efficiency of the comprehensive model for the frontlighting system.
Keywords: model reduction; modal description; flexible multibody systems

Aspects of Flexible Viscoelastic Suspension Modeling for Frictional Rolling Contact Analysis using ADAMS - Kohl, Sergej; Sextro, Walter; Schulze, Sebastian (The 2nd International Conference on Automotive Innovation and Green Energy Vehicle (AiGEV 2016), Cyberjaya, Malaysia, 2016.)
Tire-wheel assembly is the only connection between road and vehicle. Contacting directly with road within postcard size of contact area, it is mounted and guided by the suspension system. Therefore kinematics and compliances of suspension system greatly influence the frictional coupling of tire tread elements and road surface asperities by affecting pressure and sliding velocity distribution in the contact zone. This study emphasizes the development of a numerical methodology for frictional rolling contact analysis with focus on interaction of suspension system dynamics and tire-road contact using ADAMS. For this purpose a comprehensive flexible multibody system of the multi-link rear suspension is established, where both flexible and rigid bodies are modeled to allow large displacements with included elastic effects. To meet accuracy requirements for the high frequency applications, such as road excitations, the amplitude- and frequency-dependency of rubber-metal bushings is included. Furthermore the proposed flexible viscoelastic suspension model is enhanced by a Flexible Ring Tire Model (FTire), which describes a 3D tire dynamic response and covers any road excitations by tread submodel connected to road surface model. Concerning the verification and validation procedure numerous experiments are carried out to confirm the validity and the accuracy of both the developed submodels and the entire model. The devised approach makes it possible to investigate the influence of suspension system design on dynamical rolling contact and to evaluate tire tread wear. Therefore it can be a useful tool to predict frictional power distribution within the contact area under more realistic conditions.
Keywords: Kinematics and compliances; flexible viscoelastic suspension model; frictional rolling contact analysis; frictional power distribution.

Transportation of dry fine powders by coordinated friction manipulation - Dunst, Paul; Sextro, Walter; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter (PAMM Proc. Appl. Math. Mech. 16)
The transportation of dry fine powders is an emerging technologic task, as in biotechnology, pharmaceutical or coatings industry particle sizes of processed powders are getting smaller and smaller. Fine powders are primarily defined by the fact that adhesive and cohesive forces outweigh the weight forces. This leads to mostly unwanted agglomeration (clumping) and adhesion to surfaces, what makes it more difficult to use conventional conveyor systems (e. g. pneumatic or vibratory conveyors) for transport. A rather new method for transporting these fine powders is based on ultrasonic vibrations, which are used to reduce friction and adhesion between powder and the substrate. One very effective set-up consists of a pipe, which vibrates harmoniously in axial direction at low frequency combined with a pulsed radial high frequency vibration. The high frequency vibration accelerates the particles perpendicular to the surface of the pipe, which in average leads to lower normal and thereby smaller friction force. With coordinated friction manipulation the powder acceleration can be varied so that the powder may be greatly accelerated and only slightly decelerated in each excitation period of the low frequency axial vibration of the pipe. The amount of powder flow is adjustable by vibration amplitudes, frequencies, and pulse rate, which makes the device versatile for comparable high volume and fine dosing using one setup. Within this contribution an experimental set-up consisting of a pipe, a solenoid actuator for axial vibration and a piezoelectric actuator for the radial high frequency vibration is described. An analytical model is shown, that simulates the powder velocity. Finally, simulation results are validated by experimental data for different driving parameters such as amplitude of low frequency vibration, pipe material and inclination angle.

Entwurf und Anwendung einer erweiterten Zustandsüberwachung zur Verlässlichkeitssteigerung selbstoptimierender Systeme - Sondermann-Woelke, Christoph
Das Wirkparadigma der Selbstoptimierung ermöglicht mechatronischen Systemen sich autonom und flexibel an veränderte Betriebssituationen anpassen zu können. Um selbstoptimierende Systeme verlässlich zu gestalten und darüber hinaus Selbstoptimierung zur Verlässlichkeitssteigerung des Systems zu nutzen, werden in dieser Arbeit der Entwurf und die Anwendung einer erweiterten Zustandsüberwachung dargestellt. Darin wird eine klassische Zustandsüberwachung mit dem Wirkparadigma der Selbstoptimierung verbunden. Für den Entwurf der erweiterten Zustandsüberwachung wird aufgezeigt, welche Schritte erforderlich sind, damit das Wirkparadigma der Selbstoptimierung genutzt und gleichzeitig das selbstoptimierende System abgesichert werden kann. Die Basis für den Entwurf der erweiterten Zustandsüberwachung stellt die Spezifikation der Prinziplösung selbstoptimierender Systeme dar. So können das System und die erweiterte Zustandsüberwachung in den frühen Phasen des Entwicklungsprozesses konsistent entworfen werden. Hinsichtlich der Anwendung werden drei Aspekte betrachtet. Erstens werden die Entwurfsschritte anhand des Anwendungsbeispiels umgesetzt und bewertet. Zweitens werden die unterschiedlichen Betriebsstrategien auf einem realen Demonstrator implementiert und erprobt, um vor allem das Konzept des Umschaltens auf verlässlichkeitsorientierte Ziele im Fehlerfall zu bewerten. Drittens werden Simulationen durchgeführt, die über die Möglichkeiten des realen Demonstrators hinausgehen. Die exemplarische Anwendung zeigt, dass die erweiterte Zustandsüberwachung eine Steigerung der Verlässlichkeit im Betrieb mittels Selbstoptimierung ermöglicht.
Keywords: Verl{\

Modeling and simulation of the ultrasonic wire bonding process - Meyer, Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (2015 17th Electronics Packaging Technology Conference)
Ultrasonic wire bonding is an indispensable process in the manufacturing of semiconductor components. It is used for interconnecting the silicon die to e.g. connectors in the housing or to other semiconductors in complex components. In high power applications, such as wind turbines, locomotives or electric vehicles, the thermal and mechanical limits of interconnects made from aluminum are nearing. The limits could be overcome using copper wire bonds, but their manufacturing poses challenges due to the harder material, which leads to increased wear of the bond tools and to less reliable production. To overcome these drawbacks, adaptation of process parameters at runtime is employed. However, the range of parameter values for which a stable process can be maintained is very small, making it necessary to compute suitable parameters beforehand. To this end, and to gain insights into the process itself, the ultrasonic bonding process is modeled. The full model is composed of several partial models, some of which were introduced before. This paper focuses on the modularization of the full model and on the interaction of partial models. All partial models are presented, their interaction is shown and the general outline of the simulation process is given.

Modeling of the Stick-Slip Effect in Heavy Copper Wire Bonding to Determine and Reduce Tool Wear - Unger, Andreas; Sextro, Walter; Meyer, Tobias; Eichwald, Paul; Althoff, Simon; Eacock, Florian; Brökelmann, Michael (2015 17th Electronics Packaging Technology Conference)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tool tip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard's wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.

Improving the cleaning process in copper wire bonding by adapting bonding parameters - Althoff, Simon; Unger, Andreas; Sextro, Walter; Eacock, Florian (2015 17th Electronics Packaging Technology Conference)
Changing manufacturing technologies or material in well-known processes has to be followed by an adaption of process parameters. In case of the transition from aluminum wire to copper wire in heavy wire bonding, the adaption effort is high due to the strongly different mechanical properties of the wire. One of these adaption aspects, apart from wire material, is the existent oxide layers on wire and substrate. The ductile aluminum oxide is not influencing the bonding process much, because it is supposed to break apart in case of plastic deformation. The lubricating copper oxide layer has to be removed before micro welds can develop. Therefore, in this paper, experiments are carried out at low frequency to determine the friction energy needed to abrade the copper oxide layer of wire and substrate, which is indicated by an increase in the resulting friction coefficient. The friction energy per contact area to remove the interfering layers at low frequency is compared to the real bonding process working at 58 kHz. In addition, a theoretical concept is being described to get a grasp of the occurring mechanism. In the end a proposal is given how to set bonding parameters to get the cleanest surfaces with the installed bond tool.

Anforderungen an Condition-Monitoring-Verfahren zur Nutzung im zuverläsigkeitsgeregelten Betrieb adaptiver Systeme - Meyer, Tobias; Kimotho, James Kuria; Sextro, Walter (27. Tagung Technische Zuverlässigkeit (TTZ 2015) - Entwicklung und Betrieb zuverlässiger Produkte)
Intelligente technische Systeme, die in der Lage sind, sich an geänderte Umgebungsbedingungen anzupassen, ermöglichen eine Adaption anhand der aktuell erreichten Zuverlässigkeit. Zu diesem Zwecke kann ein geschlossener Regelkreis formuliert werden, der dazu geeignet ist, den Betriebspunkt des Systems während der gesamten Lebensdauer anzupassen. Dadurch wird eine harte Umschaltung während des Betriebs vermieden und die Verhaltensanpassung ist vom Nutzer weitgehend unbemerkt möglich. Dazu wird die aktuelle Restlebensdauer mit einer vorgegebenen Restlebensdauer verglichen. Durch Änderung der vorgegebenen Restlebensdauer lässt sich auch eine Anpassung der gewünschten Nutzungsdauer erreichen, beispielsweise um veränderte Wartungsintervalle einzuhalten. Zu diesem Zwecke ist es allerdings notwendig, die aktuell erreichte Zuverlässigkeit zu schätzen. Für die Regelung ist dabei die aktuelle Restlebensdauer der wichtigste Parameter, da er als Istwert direkt mit der gewünschten Restlebensdauer als Sollwert verglichen wird und als Reglereingang dient. Für die Genauigkeit der Regelung ist daher die Bestimmung der Restlebensdauer von entscheidender Bedeutung. Es wird ein Modell des Regelkreises vorgestellt, das auch den Einfluss einer fehlerhaften Restlebensdauerschätzung auf die Verhaltensanpassung abbildet. Dadurch ist es möglich, Grenzen der Verhaltensanpassung und die zur Einhaltung notwendige Genauigkeit der Restlebensdauerschätzung zu bestimmen. Es gibt zahlreiche Ansätze, die Restlebensdauer zu schätzen, die aufgeteilt werden in modellbasierte Verfahren und datengetriebene Verfahren. Die individuelle Eignung eines jeden Verfahrens sowie die Modellbildung oder die Nutzung geeigneter Algorithmen ist stark systemabhängig. Um die Auswahl von Verfahren und Modellen oder Algorithmen zu ermöglichen, werden zunächst die Anforderungen an die Restlebensdauerschätzung zur Nutzung als Regelungs-Istwert bestimmt. Verschiedene Verfahren werden sodann hinsichtlich ihrer Eignung evaluiert und Anwendungsgrenzen aufgezeigt.

Integrated Model for Dynamics and Reliability of Intelligent Mechatronic Systems - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (European Safety and Reliability Conference (ESREL2015))
Intelligent mechatronic systems are able to autonomously adapt system behavior to current environmental conditions and to system states. To allow for such reactions, complex sensor and actuator systems as well as sophisticated information processing are required, making these systems increasingly complex. However, with the risk of increased system complexity also comes the chance to adapt system behavior based on current reliability and in turn to increase reliability. The adaptation is based on switching selecting an appropriate working point at runtime. Multiple suitable working points can be found using multi-objective optimization techniques, which require an accurate system model including system reliability. At present, modeling of system reliability is a laborious manual task performed by reliability modelling experts. Despite actual system reliability being highly dependent on system dynamics, pre-existing system dynamics models and the resulting reliability model are at best loosely coupled. To allow for closer interaction among dynamics and reliability model and to ensure these are always synchronized, advanced modeling techniques are required. Therefore, an integrated model is introduced that reduces user input to a minimum and that integrates system dynamics and system reliability.

Integrierte Modellierung der Dynamik und der Verlässlichkeit komplexer mechatronischer Systeme - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (10. Paderborner Workshop Entwurf mechatronischer Systeme)
Die starke Integration von Sensorik, Aktorik, Hard- und Software stellt Herausforderungen an die Verlässlichkeit intelligenter mechatronischer Systeme dar. Diese Systeme verfügen aber auch über großes Potential zur Verbesserung ihrer Verlässlichkeit durch eine Anpassung des Systemverhaltens an den aktuellen Zustand. Um den Umfang der Systemmodelle zu reduzieren und die Anpassung des Systemverhaltens zu ermöglichen, sind fortschrittliche Modellierungsmethoden notwendig, mit denen die Verlässlichkeit in frühen Phasen des Entwicklungsprozesses sichergestellt und evaluiert werden kann. Von den Attributen der Verlässlichkeit ist insbesondere die Zuverlässigkeit in hohem Maße von den auftretenden Belastungen an den Komponenten und damit vom dynamischen Systemverhalten abhängig. Bisherige Modellierungsansätze bilden diese Abhängigkeit nur unzureichend ab. Es wird daher ein Ansatz zur integrierten Modellierung mechatronischer Systeme vorgestellt. Dieser ist in der Lage, sowohl die Dynamik als auch die Zuverlässigkeit des Systems abzubilden. Die Transformation eines Modells des dynamischen Systemverhaltens generiert dabei ein Zuverlässigkeitsmodell. Für typischerweise konkurrierende Ziele können mit Hilfe von Mehrzieloptimierungsverfahren Betriebspunkte eines Systems bestimmt werden. Das integrierte Modell kann zur Erzeugung von Zielfunktionen für die Dynamik als auch für die Zuverlässigkeit genutzt werden. Die Ergebnisse ermöglichen eine Verhaltensanpassung durch Wahl eines paretooptimalen Betriebspunkts während des Betriebs. Das vorgeschlagene Konzept zur integrierten Modellierung mechatronischer Systeme bietet aufgrund des modellbasierten Entwicklungsansatzes und der automatisierten Transformation eines Verlässlichkeitsmodells eine Reduktion der Benutzereingaben und eine Entlastung des Benutzers. Dadurch wird die Wahrscheinlichkeit von Benutzerfehlern gesenkt und die Verlässlichkeit bereits während der Entwicklung erhöht. Somit können Iterationsschleifen vermieden und die Entwicklungskosten gesenkt werden.
Keywords: Verlässlichkeit; Zuverlässigkeit; Dynamik; integrierte Modellierung

Thick KNbO 3 films deposited by ultrasonic-assisted hydrothermal method - Kudo, Ryo; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Acoustical Science and Technology)

A Mechanical Model for the Dynamical Contact of Elastic Rough Bodies with Viscoelastic Properties - Schulte, Frank; Neuhaus, Jan; Sextro, Walter (Proceedings of ICoEV 2015 International Conference on Engineering Vibration)
The contact between viscoelastic materials e.g. elastomers and a rough surface leads to a special friction characteristic, which differs greatly in its properties comparing to other materials like metals. In practice, this friction combination occurs for example in the tire-road contact, or in the use of rubber gaskets. Due to the frictional forces a system is significantly influenced in its vibrational properties. The friction force is composed of two main components adhesion and hysteresis. The adhesion results from molecular bounds between the contact partners, while the deformation of the viscoelastic material by the roughness of the counter body leads to power loss. This internal friction results in an additional frictional force, which is described by the hysteresis. To simulate the frictional behaviour of elastomers on rough surfaces and thus to determine the energy dissipation in contact, it is necessary to develop a mechanical model which considers the roughness of the contact partners, as well as dynamic effects and the dependence on normal pressure and sliding speed. The viscoelastic material behaviour must also be considered. The contact between two rough surfaces is modelled as a rough rigid layer contacting a rough elas- tic layer. The elastic layer is modelled by point masses connected by Maxwell-elements. This allows the viscoelastic properties of the elastomer to be considered. The behaviour of whole system can be described by equations of motion with integrated constraints. The degrees of freedom of the model depends on the varying contact conditions. A point mass not in contact has two degrees of freedom. A point mass in contact moving along the roughness path can be described by only one degree of freedom. For each Maxwell-Element also an inner coordinate and thus a further degree of freedom is needed. Because of varying contact conditions dur- ing the simulation, the simulation interrupts in case the contact conditions change. Then the equations of motions are adapted with respect to the contact constraints. As a result of the simulation one obtain the energy dissipation and thus the friction char- acteristic during the friction process. It is possible to use these results in three dimensional point-contact elements in order to model contact surfaces on lager length scales.
Keywords: Contact Mechanics; Viscoelastic Material; Adhesive Friction; Hysteresis Friction; Energy Dissipation; Vibration

Kavitationsdetektion mittels Self-Sensing-Ultraschallwandler - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (tm - Technisches Messen)
Eine Vielzahl von Prozessen in der Chemie und Verfahrenstechnik kann durch Ultraschall positiv beeinflusst werden. Oftmals ist ultraschallinduzierte Kavitation der Hauptwirkmechanismus für die positiven Effekte der Beschallung. Daher ist es notwendig die Kavitationsaktivität während des Prozesses zu quantifizieren um die Beschallung für den jeweiligen Prozess optimal gestalten und überwachen zu können. Eine Möglichkeit der prozessbegleitenden Kavitationsdetektion ist die Auswertung der akustischen Emissionen von oszillierenden und kollabierenden Kavitationsblasen mittels Drucksensoren in der Flüssigkeit. Raue Prozessrandbedingungen wie hohe Temperaturen oder aggressive Flüssigkeiten erschweren es jedoch geeignete Sensoren zu finden. Als Alternative wurde daher die Nutzbarkeit der Rückwirkung von Kavitationsereignissen auf das elektrische Eingansgssignal des Ultraschallwandlers zur Quantifizierung von Kavitation untersucht. Die experimentelle Analyse hat ergeben, dass das Einsetzen und in einigen Fällen auch die Art der Kavitation auf Basis der Rückwirkung auf das Stromsignal des Ultraschallwandlers bestimmt werden kann. Die Stärke der Kavitation war hingegen nicht aus den Stromsignalen abzuleiten.
Keywords: Kavitationsdetektion; Self-Sensing; So- nochemie; Ultraschallwandler